Long-term mineral fertilization increases microbial carbon use efficiency and necromass in upland but not in paddy soils - Ziyi Li; Di Lin; Huimin Zhang; Chengjie Ren; Yu'’e Li; Andong Cai (CATENA, 2026)

Monoterpenoid bisindole alkaloids with intestinal anti-inflammatory activity from Kopsia hainanensis - Jiamin Wang; Niping Li; Zhuoying Lin; Su Nie; Jiabin Huang; Di Zhang; Yiyi Li; Jian Hong; Wencai Ye; Lei Wang (Phytochemistry, 2026)

Insights from stratigraphic reconfiguration induced by the South Pole-Aitken massive impact - Sheng Gou; Zongyu Yue; Yangting Lin; Bin Su; Zhanchuan Cai; Roberto Bugiolacchi; Kaichang Di; Patrick C. Pinet; Yuyang He; Honglei Lin; Hengci Tian; Sen Hu; et al. (Icarus, 2026)

Photothermal antibacterial bilayer films from konjac glucomannan/shellac: A Prussian blue-engineered strategy for preservation of fresh-cut Benincasa hispida - Xin Lei; Yueguang Wang; Xianrui Chen; Jing Zhang; Xuan Lin; Wenjun Guo; Xiuqing Guan; Chengrong Wen; Di Zhang; Lin Wang; Jie Pang (Food Research International, 2026)

Effects of sustained eccentric loading on concrete-encased concrete-filled steel tubular (CFST) columns - Zhi-Cheng Yang; Di Fan; Guan-Yuan Zhao; Li Zhu; Lin-Hai Han; Chen-Yu Zhang (Engineering Structures, 2026)

An enhanced YOLO-based deep learning framework for automated structural defect inspection in complex backgrounds - Zheyu Liu; Di Su; Youqi Zhang; Da-Wei Lin; Zhen Sun (Engineering Structures, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Spearman rank analysis and dynamic contact stress concentration model of Brazilian splitting fracture behavior of coal samples under impact load - Kong Xiangguo; Rong Zhihao; Ma Yankun; Lin Haifei; Xiao Peng; He Di; Ji Pengfei; Zhu Yanhui (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

The dominant π-π interaction in the adsorption of humic acids onto carbonized cuttlebone: Evidence from UV spectrophotometry and bleaching experiments - Xiaoao Bai; Bin Wang; De Wang; Hui Jiang; Lin Shi; Wenlin Xu; Di Zhang (Journal of Water Process Engineering, 2026)

A high-throughput strategy for screening umami peptides from Chouguiyu based on peptidomics and machine learning-assisted molecular simulation - Sitong Lyu; Shichao Xuan; Fan Yang; Honglin Yu; Di Meng; Jianqing Zhou; Cristabelle De Souza; Zhe Zhang; Tongjie Liu; Huaxi Yi; Qingjuan Tang; Lanwei Zhang; et al. (Food Research International, 2026)

Synergistic co-culture of Rhizopus oryzae and Rhodotorula babjevae transforms faba bean and oat into nutrient-rich tempeh-like foods - Laura Alejandra Fernandez Castaneda; Galia Zamaratskaia; Su-lin L. Leong; Volkmar Passoth; Chiara Viretto; Ali Zein Alabiden Tlais; Raffaella Di Cagno; Fabio Tuccillo; Minnamari Edelmann; Kati Katina; Olivia Zehnder-Wyss; Laura Nyström; et al. (Food Research International, 2026)

Ultrasensitive and rapid detection of botulinum neurotoxin serotype A via Argonaute-mediated signal cascade with a pregnancy test strip readout - Weiling Yu; Yukang Chen; Shujie Zhang; Ruina Zheng; Zhanyin Lin; Yujun Mei; Qiancheng Zhan; Bowen Xue; Jinxuan Fan; Bo Liu; Song Gao; Yuan-Di Zhao; et al. (Food Chemistry, 2026)

A novel dandelion-like chitosan-based aerogel microsphere with multi-crosslinked 3D porous network toward promising multi-functional application - Wuyou Wang; Longkang Di; Xiaowen Zhao; Lin Ye (Chemical Engineering Journal, 2026)

Decoupling the synergy of dipole moment and planarity in donor–acceptor conjugated polymers via bridge atom engineering for photocatalytic H₂ evolution - Ke Wang; Lin Wang; Di Wang; Zhaohang Ben; Yucheng Liu; Bo Cheng; Zongzhao Liu; Qiang Zhang; Yan Lu (Chemical Engineering Journal, 2026)

Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

S100 signaling in hair follicle biology: emerging mechanistic insights and therapeutic opportunities - Dongfan Wei; Hongwei Jia; Lin Shang; Di Zhang; Fenglin Zhuo (Journal of Molecular Histology, 2026)

Pyridyl ethyl diazoacetate derivatization enables LC-MS annotation of cholesterol and its metabolites - Wenhao Ke; Yikang Wang; Yang Chen; Hanchu Ye; Wen-Di Duan; Feifei Lin; Yingying Wang; Zhengjun Zhou; Zhiyong Yu; Youhong Hu; Jia Liu (Analytica Chimica Acta, 2026)

Development of a Recombinant Goose Parvovirus VP2 Neutralizing Epitope-Containing Region Vaccine Adjuvanted with IL-2 and FliC for Enhanced Immune Responses and Protection Against Challenge - Qing Wu; Xinyu Li; Jiaxin Li; Ziran Liu; Lin Bai; Lin Zhang; Shujing Xia; Di Wu; Yuhan Jin; Xinyuan Shen; Yu Gao; Jingming Wang; et al. (The Veterinary Journal, 2026)

Halorubrum marinum sp. nov., Halorubrum rarum sp. nov., Halorubrum wangae sp. nov., Halorubrum shenae sp. nov., and Halorubrum zhoui sp. nov., halophilic archaea from coastal tidal flats, a saline lake, and a marine solar saltern - Qing-Di Li; Yang-Yang Wang; Chidiebele Nwankwo; Yao Hu; Xin-Yue Dong; Jing Hou; Xiang-Dong Chen; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Lactobacillus helveticus MB2-1 powders prepared using different drying strategies reshape dominant intermolecular interaction patterns and structural network formation during fermentation of coconut-based yogurt alternatives - Jianwei Zang; Yimeng Kou; Yibo Shi; Xiaotong Hao; Shiyuan Feng; Chunling Meng; Jiamin Xu; Di Yu; Tao Lin; Kai Ma; Changliang Zhang; Mingsheng Dong; et al. (Food and Bioproducts Processing, 2026)

Quantitative assessment of factors affecting reflectance retrieval from spectroscopic radiance images - Sheng Gou; Zongyu Yue; Bin Xie; Zhanchuan Cai; Honglei Lin; Yangting Lin; Kaichang Di (Advances in Space Research, 2026)

LC-MS-based metabolomics reveals the In Vivo effects of cognitive formula 1 in rats with Aβ-induced Alzheimer’s disease - Di Wu; Yanling Lin; Wenjun Guo; Zengling Wang; Yan Chang; Jing Yan; Daqing Han; Ke Xiang; Zhen Yang (Experimental Brain Research, 2026)

An algorithm for eliminating block effects in remote sensing images based on colour and texture feature fusion - Haibiao Li; Di Lin (International Journal of Remote Sensing, 2026)

Oncorhynchus mykiss as a Salmonid Functional Genomics Model: A Structured Narrative Review of Genomic Resources, Mucosal Immunity, Disease Resistance, Environmental Stress, and Causal Validation - Zhongquan Jiang; Sijia Wu; Yong Zheng; Di Peng; Siping Li; Yuanhao Ren; Bo Qin; Hanfeng Zheng; Lei Li; Tingting Lin (Fishes, 2026)
Rainbow trout (Oncorhynchus mykiss) is an important cold-water aquaculture species and a tractable salmonid model for functional genomics. Rapid advances in chromosome-level genome assemblies, genetic variation resources, regulatory annotations, tissue and cell models, controlled challenge systems, and genome-editing technologies have established an increasingly integrated framework for linking genomic variation with measurable phenotypes. Evidence from studies of mucosal immunity, disease-resistance genetics, and environmental stress responses indicates that these resources can improve candidate-gene prioritization and mechanistic interpretation across molecular, cellular, tissue, and whole-fish levels. However, differential gene expression, quantitative trait locus and genome-wide association signals, genomic predictions, and cell-type localization remain largely associative and rarely provide direct evidence of causality. Interpretation is further complicated by salmonid-specific whole-genome duplication, because retained paralogues may exhibit tissue-specific divergence, functional redundancy, and compensatory responses. Further progress will require the integration of pangenomics, regulatory annotation, single-cell and spatial analyses, and paralogue-aware functional perturbation in both cell-based and whole-fish systems. Such integration will strengthen causal inference, clarify genotype–phenotype relationships, and support disease-resistant breeding, healthy aquaculture, and environmental risk assessment.

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Amino Acid Metabolic Remodeling in Bivalves Under Environmental Stress: Roles, Mechanisms, and Implications for Bivalve Health—A Review - Yichen Lin; Wei Chen; Jixing Peng; Xinnan Zhao; Yan Di; Mengmeng Guo; Yanfang Zhao; Haiyan Wu; Guanchao Zheng; Qianqian Geng; Zhijun Tan (Fishes, 2026)
Climate change and increasing instability in coastal marine environments have intensified stressors such as elevated temperature, hypoxia, salinity variation, and pollutant exposure, posing major challenges to the survival, health, and culture performance of bivalves. As economically important aquaculture species and key components of coastal ecosystems, bivalves are highly sensitive to environmental fluctuations, making their metabolic responses highly relevant to both physiological adaptation and aquaculture sustainability. Increasing evidence indicates that metabolic remodeling is an important adaptive strategy supporting bivalve tolerance to environmental stress, with amino acid metabolic remodeling emerging as one of its most sensitive and functionally important components. This review summarizes the major response patterns, key pathways, and potential regulatory mechanisms of amino acid metabolism in bivalves under different stress conditions. Different environmental stressors induce distinct yet integrated shifts in amino acid metabolism, including enhanced catabolism, carbon–nitrogen redistribution, osmotic regulation, and antioxidant defense, thereby supporting energy homeostasis and physiological stress tolerance in bivalves. By highlighting amino acid metabolic remodeling as a central mechanism of bivalve adaptation to environmental stress, this review provides insights into adaptive responses, metabolite-based indicators for monitoring aquaculture environments and bivalve health, and management strategies for improving resilience in bivalve aquaculture.

Light-TDNN: A lightweight acoustic model for panic stress recognition of caged laying hens in intensive farms - Zheng Wang; Binfeng Chen; Mengzui Di; Jintian Chen; Shupeng He; Hongjian Lin; Canyu Wang; Jinming Pan (Computers and Electronics in Agriculture, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Impacts of steam explosion treatment on qualities, protein network development and digestion-resistant properties of dried sorghum noodles - Kun Yu; Xiaoli Ma; Jingjie Lin; Yuan Zhang; Chunxu Chen; Di Wu; Peiyan Li; Guoyuan Xiong (Food Chemistry, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Beyond pyrolysis optimization: a systematic review revealing feedstock acquisition and methodological standardization as critical barriers to biochar commercialization - R. B. Sherly Priyanka; Uday Shashikumar; Pei-Chien Tsai; Swapnil Gurrani; Gangadhar Andaluri; Cheng-Di Dong; Chyi-How Lay; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Clean Technologies and Environmental Policy, 2026)

Unraveling the complex interplay between glymphatic function, age, and brain structure in school-aged children with autism spectrum disorder - Zhongfeng Xie; Di Zhou; Shuchao Wang; Ting Hua; Hong Chen; Rong Yang; Yujiao Gong; Guangyu Tang; Lin Zhang; Xiaowen Xu (Brain Imaging and Behavior, 2026)

Ecological water replenishment enhances nitrogen removal potential in coastal wetlands by mediating root exudate composition and sediment chemistry - Chunyu Zhao; Songlin Liu; Junliang Wang; Naiqin Zhang; Jingqi Lin; Nana Liu; Kai Di; Donghan Zhang; Changwen Ma; Yang Liu (Marine Pollution Bulletin, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

The domestication-associated WHP10 tandem cluster of amino acid transporter genes enhances whole-plant protein accumulation in maize - Wenhao Li; Youliang Li; Xiang Lin; Ruilin Chen; Wenjing Li; Chong You; Di Chen; Lulu Gao; Xiaoling Li; Shiqi Luo; Yunlong Li; Yuhua Long; et al. (Molecular Plant, 2026)

Cooling history and source characteristics of the Chang'e-6 low-Ti basalt: Constraints from plagioclase - Di Zhang; Wei Yang; Huijuan Zhang; Honggang Zhu; Yunhong Fan; Hengci Tian; Shitou Wu; Lihui Jia; Lixin Gu; Yangting Lin (Icarus, 2026)

Eco-friendly wheat straw-reinforced MICP for sand stabilization: Enhancing solidification uniformity and modeling freeze–thaw pore damage - Xinyue Zhang; Zihua Li; Qiang Jin; Zhenhao Zhou; Di Hu; Lin Zhu (Engineering Geology, 2026)

Metal-air fuel cells for phosphorus recovery from wastewater: A critical analysis of principles, progress, and application perspectives - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Yuan Liu (Chemical Engineering Journal, 2026)

Microfluidic-based magnetic microspheres for targeted delivery of curcumin nanoparticles in gastroesophageal reflux disease therapy - Haoyao Jiang; Zhonglin Fang; Han Lin; Di Xu; Wanqian Xu; Mengqi Han; Luoran Shang; Ye Zhao; Teng Ma; Di Ge (Chemical Engineering Journal, 2026)

Direct recovery of silver and simultaneous purification of silicon from end-of-life photovoltaic modules via a one-step hydrothermal method - Danyan Qin; Kai Zhang; Shihao He; Xian Xie; Jie Liu; Long Peng; Yingzhu Li; Di Wu; Yaokai Zhong; Yun Shen; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2026)

Effect of impeller design and operating conditions on food waste hydrolysis: Insights from experiments and computational fluid dynamics simulations - Yahui Miao; Di Wu; Siqi Wang; Muhammad Ahmar Siddiqui; Huaimin Wang; Guneet Kaur; Sophie L.K.W. Roelants; Chi Yan Tso; Zheng Sun; Carol Sze Ki Lin (Bioresource Technology, 2026)

Redefining solid–liquid interface probing via contact electrification-driven paradigm - Xiang Li; Zhong Lin Wang; Di Wei (Science Bulletin, 2026)

Nanoplastics exacerbated renal injury amid hypertension: Rethinking health hazards in disease and implication of renal senescence and EMT associated with Sirt1 downregulation - Yi Liu; Di Ji; Yijuan Lin; Shuzi Ye; Rong Guo; Zidie Luo; Fang Xiao (Environmental Pollution, 2026)

Controlled in situ semi-conversion strategy for fabricating a “embedded-covering type” FeCo-LDH/Ag/MIL-88B Z-scheme heterojunction: efficient meloxicam removal via adsorption-photodegradation and enhanced antibacterial activity - Xinru Lin; Di Sun; Zonghe Yu; Junyang Zhang; Peng Yan; Yang Wang; Yuzhong Gao (Desalination, 2026)

Environmental potential of food waste-derived bioplastics - Zi-Hao Qin; Di Wu; Anda Fridrihsone; Mikelis Kirpluks; Carol Sze Ki Lin (Current Opinion in Green and Sustainable Chemistry, 2026)

A Multi-Objective Optimization Model of Coupled Grey-Green Stormwater Infrastructure Based on PSO-NSGA-III: A Perspective Considering Drainage Pipeline Desilting Schemes - Zhaoyang Zhang; Hongyuan Fang; Danyang Di; Kairong Lin; Meixian Liu (Water Resources Management, 2026)

A tuning-free POD-FV-ROM with automatic boundary enforcement for practical thermal-hydraulic applications - Yang Di; Zhang Chunyu; Lin Jiming; Ding Peng (Annals of Nuclear Energy, 2026)

Shenrong Guben Huanshao Pill enhanced stress resistance and extended the lifespan of Caenorhabditis elegans by activating the oxidative stress system via the DAF-16/FOXO signaling pathway - Yi-Nan Yang; Xin Wang; Hong-Fen Jiang; Jie Yang; Subiy Akbara; Xiao-Qin Yang; Hai-Qing Fan; Guo-Lin Chai; Dong-Qing Fei; Fang-Di Hu; Shuang-Xi Qian; Zhan-Xin Zhang (Biogerontology, 2026)

SlCNR promotes the lycopene accumulation and reduces abscisic acid content in postharvest tomato fruit - Shuai Zhang; Mingzhe Mang; Di Chen; Liqun Ma; Shiyuan Zhang; Tingting Hu; Lin Yu; Jiankang Cao; Daqi Fu; Benzhong Zhu; Hongliang Zhu; Guiqin Qu (Postharvest Biology and Technology, 2026)

Viral communities as mirrors and vectors: Tracing antibiotic resistome distribution and dissemination across diverse habitats in Macao - Yu-Qiu Ye; Da Lin; Luo-Qin Shen; Di Wu; Ying Li; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2026)

Enhanced photoreduction of perfluorooctane sulfonate via a confined nitrilotriacetic acid system augmented by CTAB - Zhenyu Zhai; Yunmeng Zhao; Chaojie Zhang; Xuefei Zhou; Yalei Zhang; Sijie Lin; Xueran Xu; Xiang Liu; Di Huang; Yingping Huang; Cheng Gu (Journal of Hazardous Materials, 2026)

A new Rhizomucor miehei lipase immobilized on anhydride-hydrophobized amino supports: Optimization, characterization and application in preparing medium- and long-chain structured lipids - Yiyi Lin; Xiansi Gao; Zheling Zeng; Di Kuang; Kai Fang; Tianyi Song; Ping Yu; Deming Gong; Cheng Zeng; Xianghui Yan (Food Bioscience, 2026)

Two-level energy storage semi-interpenetrating hydrated salt gel for battery cooling and thermal runaway propagation mitigation - Rui Wei; Yuhan Xiao; Jianfeng Wang; Fuqiang Wang; Di-Lin Chen; Bowei Chen; Zipeng Su; Yongkai Jia; Ruixuan Qiu; Yiqun Liu; Quanqing Yu; Fen Liu (Chemical Engineering Journal, 2026)

Loofah-inspired recyclable MXene/polypyrrole fiber-skeleton hydrogels for machine-learning-assisted multimodal flexible sensor - Zhiyang Li; Chendan Cui; Fan Yang; Di Yuan; Hemiao Wang; Zhaoyun Lin; Lupeng Shao; Qiang Wang; Weikun Jiang; Linglong Shi; Yu Liu; Dehai Yu (Chemical Engineering Journal, 2026)

Surface-interface tribo-charge as a fundamental factor for efficient energy harvesting in triboelectric nanogenerators - Di Wang; Yuhe Guo; Zhong Lin Wang; Baodong Chen (Chemical Engineering Journal, 2026)

The vinculin-β-catenin axis promotes bone formation and repair: an essential prerequisite for the anti-osteoporotic efficacy of sclerostin-neutralizing antibody - Sixiong Lin; Chu Tao; Yishu Wang; Jianglong Li; YuJia Shi; Qinnan Yan; Yiming Zhong; Huanqing Gao; Tingxuan Wang; Yibo Wang; Qing Yao; Jianmei Huang; et al. (Science China Life Sciences, 2026)

Mechanisms of cold adaptation in a novel marine eukaryotic phytoplankton—psychrophilic microalga Chlamydomonas sp. LWD-1 - Di Zhang; Songlin Ma; Gerui Yin; Shuo Lin; Bailing Chen; Keqing Liu; Weidong Liu; Yiwen Chen; Baolin Jia; Zhanyou Chi; Fantao Kong (Plant Cell Reports, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Bidirectional gut-heart axis interactions in the context of predictive, preventive, and personalised medicine: a time-course analysis of comorbidity and mortality risk in a large population cohort - Meiling Cao; Di Liu; Haotian Wang; Cancan Li; Huapeng Lin; Lijuan Wu; Youxin Wang (EPMA Journal, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

A partitioned coupling framework for occupant head injury assessment under water entry impact of a free-fall lifeboat - Ningge Fan; Gong Chen; Shunhua Chen; Yingying Lin; Di Wang (Ocean Engineering, 2026)

Performance evaluation of near-field localization for artificial lateral line based on theoretical analysis and orthogonal test - Haoxun Yuan; Yingchun Xie; Guijie Liu; Di-Lin Chen; Jinchi Zhu; Jie Liu; Songping Meng (Ocean Engineering, 2026)

Strategy for optimization of auto-driven electrochemical module towards phosphorus recovery from wastewater: Performance and mechanism of electric field regulation - Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Hao-Ran Yang; Ying Chen; Qi Kuang; Yuan Liu (Journal of Cleaner Production, 2026)

Nanomaterials in the food industry: applications and potential health risks - Wenrui Li; Suyu Lin; Luyao Zhang; Jiachen Yu; Yuling Cai; Di Wu; Yongning Wu; Guoliang Li (Food Chemistry, 2026)

Temperature-induced structural responses of a long-span suspension bridge: A digital twin approach - Ning-Jie Zhou; You-Lin Xu; Zi-Jing Wei; Di Wu; Er-Hua Zhang (Engineering Structures, 2026)

Supramolecularly cross-linked aramid-PVDF-aramid sandwich electrolytes with continuous Li+ pathways for ultralong cycle life in solid-state lithium metal batteries - Jianhong Xu; Dehua Li; Xiao Yang; Yingyuan Ma; Xinrui Zheng; Panpan Shen; Di Zhang; Weiyu Teng; Yuting Lin; Yi Hu (Chemical Engineering Journal, 2026)

Physics-informed neural network for predicting longitudinal deformation in super-large-diameter shallow-buried shield tunnel during construction - Xing-Tao Lin; Qi-Rui Lin; Rui-Di Chen; Xiangsheng Chen; Dong Su (Tunnelling and Underground Space Technology, 2026)

Engineering supersaturation for the recovery of lanthanum as lanthanum phosphate via fluidized-bed crystallization - Po-Lin Liao; Thanh Binh Nguyen; Chiu-Wen Chen; Cheng-Di Dong (Journal of Water Process Engineering, 2026)

Light-responsive biopolymeric films embedded with natural polyphenols: ROS-mediated suppression of postharvest microbial decay in perishable fruits - Xianrui Chen; Lin Wang; Lihong Lin; Nitong Bu; Di Zhang; Zhenzhen Wu; Wei Liu; Jie Pang (Food Control, 2026)

Static magnetic field programming of exosomes enhances FOXO1-driven osteo-vascular regeneration in 3D-printed titanium scaffolds - Kaiwen Zheng; Zihao Lin; Yanchun Gao; Xu Zheng; Bin Hu; Changqing Zhang; Dehao Fu; Di Wu (Chemical Engineering Journal, 2026)

Multi-omics evidence reveals acetogenesis as the primary metabolic bottleneck under ammonia stress - Yun Peng; Chunyan Lin; Hengyi Liu; Lei Li; Xuya Peng; Di Wu; Xiaofei Zhao (Bioresource Technology, 2026)

A River Hydrodynamic Surrogate Model Using Nonlinear Autoregressive with Exogenous Inputs Fourier Neural Operator - Youkun Li; Junqiang Lin; Di Zhang; Boran Zhu; Qidong Peng; Yicheng Wang; Tiantian Jin (Water Resources Management, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Beyond temperature: predictive modelling of range shifts in benthic peracarids across the northern North Pacific under future climate scenarios - Stefanie Kaiser; Anna M. Jażdżewska; Sarah Gerken; Anne Helene S. Tandberg; Chih-Lin Wei; Davide Di Franco; Hanieh Saeedi; Hannah Owens; Henry Knauber; Emma Palacios Theil; Angelika Brandt; Pedro Martinez Arbizu; et al. (Progress in Oceanography, 2026)

A new strategy of urine stabilization via in situ electrochemical acidification: Enabled by CeMn-doped cobalt spinel anode - Qi Kuang; Lin-Jiang Zhong; Di Wu; Meng-Yue Zhang; Shu-Jie Hu; Ying Chen; Yuan Liu (Journal of Environmental Chemical Engineering, 2026)

Peak load prediction and interface behavior analysis of steel–ECC composite slabs: Experiments, simulations and theoretical models - Youzhu Lin; Haijun Wang; Ming Sun; Yuanbo Hu; Di Yao; Jiachuan Yan (Engineering Structures, 2026)

Prognostic, mutational, and immunologic analysis of CD90 in pan-cancer and validation of DHDK as a drug candidate - Jingtao Zhao; Yuqing Wang; Fangyu Zhang; Xinyue Wang; Lin Meng; Jing Hong; Dingjia Guo; Xin Di; Yunli Zhao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction Note: TFAP2C Activates CST1 Transcription to Facilitate Breast Cancer Progression and Suppress Ferroptosis - Lin Yuan; Di Zhou; Weiwen Li; Jianhua Guan; Junda Li; Bo Xu (Biochemical Genetics, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Multi-objective optimization framework for enhancing the sustainability and resilience of green-grey infrastructure: A perspective incorporating the impact of pipeline siltation on flood simulation - Danyang Di; Hongyuan Fang; Zhaoyang Zhang; Kairong Lin; Meixian Liu; Hao Jia (Journal of Cleaner Production, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

New insight into deciphering the component heterogeneity of humic acid in governing carbon nanotubes dispersion - Jinfeng Zhao; Yao Lu; Lin Shi; Huang Zhang; Wenmei Tao; Fangfang Li; Di Zhang (Environmental Research, 2026)

Semi-analytical model of axial load-bearing capacity of circular defective concrete-filled steel tube columns considering local buckling - Siqi Lin; Jing Li; Di Yang; Yan-Gang Zhao (Engineering Structures, 2026)

Towards zero liquid discharge: Resource recovery and circular economy pathways via bipolar membrane electrodialysis - Hao-Ran Yang; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Ying Chen; Yuan Liu (Chemical Engineering Journal, 2026)

The chemotaxonomic significance of chemical constituents from Gynostemma pentaphyllum - Hou-Lin Peng; Man-Hui Yang; Wu-Di Zhai; Wen-Juan Li; Jing Liu; Yan Zhang (Biochemical Systematics and Ecology, 2026)

Mechanistic insights into electric field-assisted nanofiltration for efficient lithium-magnesium separation - Ao Wang; Dimitrios Toroz; Xiaofu Guo; Jie Liu; Shangming He; Liting Fei; Yingying Zhao; Shizhao Wang; Junsheng Yuan; Devis Di Tommaso; He Lin; Fei Li; et al. (Water Research, 2025)

Mechanism of gas seepage enhancement based on the evolution of micro-pores and energy dissipation in coal under dynamic load - Di He; Shugang Li; Xiangguo Kong; Haifei Lin; Yankun Ma; Yuchu Cai (Geomechanics for Energy and the Environment, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

An enhanced nanoenzyme for remodeling the inflammatory microenvironment and low-temperature photothermal cascade therapy for rheumatoid arthritis - Sui Zhou; Yong Li; Yi-Tong Zhou; Meng-Wen Ma; Kai-Lin He; Kai Cheng; Jin-Xuan Fan; Bo Liu; Ling-Li Dong; Yuan-Di Zhao; Xin Liu (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Salvigenin: a natural ally against nasopharyngeal carcinoma's malignant phenotypes and immune evasion - Di Jiang; Zhengquan Lin; Zhiqiang Mao; Ming Fu (Journal of Molecular Histology, 2025)

Early hyperferritinemia in polytrauma: a biomarker of systemic inflammation and mortality risk in a multicenter cohort study - Shunyao Chen; Teding Chang; Jialiu Luo; Cong Zhang; Peidong Zhang; Shuaipeng Gu; Zhiqiang Lin; Yujie Chen; Youxie Shen; Liming Dong; Qian Wan; Liang He; et al. (Inflammation Research, 2025)

Decision-making mechanisms for green innovation in the retail manufacturing sector - Lin Yuan; Yicheng Xu; Quanling Cai; Kaisheng Di; Jiabin Wang; Yewen Wang (Environment, Development and Sustainability, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Low Genetic Diversity and Decreased Effective Population Sizes of Acropora hyacinthus Populations Inhabiting Inshore and Offshore Reefs in the South China Sea - Yijin Di; Lingyu Zheng; Jingzhao Ke; Yinyin Zhou; Shaoyang Mo; Xiangbo Liu; Jiquan Lin; Yuxiao Ren; Duanjie Huang; Rouwen Chen; Xiubao Li (Oceans, 2025)
Coral reefs, with their high biodiversity and ecological service functions, face significant threats due to climate change, overfishing, and pollution. The South China Sea (SCS) hosts rich coral biodiversity, particularly Acropora hyacinthus, a critical species for reef restoration. However, the region’s coral reefs are increasingly degraded, highlighting the urgent need for conservation efforts. In the present study, the genetic diversity and population structure of A. hyacinthus were examined based on two types of data: double-digest restriction-site-associated DNA (ddRAD) sequencing data and mitochondrial putative control region DNA (mtCR) sequences. Coral tissue samples were collected from 74 colonies inhabiting two inshore reefs (Sanya) and three offshore reefs (Xisha islands), and 748 single nucleotide polymorphisms (SNPs) and 74 mtCR sequences were obtained and utilized for downstream analysis. The results were consistent in analyses and did not cluster into two geographical groups for the inshore and offshore sites. Phylogenetic analysis showed that individuals of A. hyacinthus inhabiting the five detected sites were likely cryptic species HyaD. Furthermore, AMOVA and pairwise FST estimations based on both data types revealed no differentiation among five populations and between inshore and offshore reefs, which could be due to the reproductive mode of broadcast spawning for this species. However, a prevalent low level of genetic diversity was observed when compared with nearby Taiwan regions and Japan, and the geographic history results showed that the effective population size (Ne) had been decreasing for the past 300 years. Thus, we speculated that the populations of A. hyacinthus inhabiting the SCS lack the potential to cope with future climate change adequately, and multiple conservation measures should be implemented based on considering genetic diversity.

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

Structure-function modulation of sodium caseinate: Insights from non-covalent reuterin binding - Mao-Cheng Sun; Jie-Ting Wang; Ying-Di Wang; Lin-Yu Hu; Shi-Qi Yu; Tiehua Zhang; Changhui Zhao (Food Chemistry, 2025)

Experimental study, finite element simulation and theoretical analysis on punching shear capacity of steel-ECC composite slabs - Youzhu Lin; Di Yao; Ge Gao; Tianfei Gu; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Quaternary-ammonium chitosan/Sericin-modified carbon nanotubes Photothermal coatings: A reusable and sustainable chemical-free seed disinfection strategy - Xianrui Chen; Lin Wang; Lihong Lin; Chen Ma; Zhenzhen Wu; Nitong Bu; Di Zhang; Wei Liu; Jie Pang; To Ngai (Carbohydrate Polymers, 2025)

Data-and experience-driven prediction method of twin shield tunneling-induced complicated settlement curve and its evolution - Rui-Di Chen; Xing-Tao Lin; Xiangsheng Chen; Hui Zeng (Tunnelling and Underground Space Technology, 2025)

Maintaining high levels of HIF-1α protects osteoarthritis cartilage by activating autophagy - Xiaolei Chen; Gangning Feng; Lufei Shao; Xue Lin; Xiaoxin He; Yong Yang; Xin Zhao; Jiangbo Yan; Long Ma; Yong Zhou; Kuanmin Tian; Hui Wang; et al. (Tissue and Cell, 2025)

PADI1 aggravates endoplasmic reticulum stress in trophoblast cells by inhibiting the FAK-ERK signaling pathway - Jianhua Ning; Songbin Yang; Fengchun Gao; Longbin Wang; Zeyu Lin; Di Cheng; Kefeng Fan (Tissue and Cell, 2025)

Machine learning and soil spectra enable rapid identification of multiple heavy metals at the continental scale - Chongchong Qi; Tao Hu; Mengting Wu; Ping Zhang; Sybil Derrible; Di Wang; Yong Sik Ok; Zhang Lin (Journal of Environmental Chemical Engineering, 2025)

Myxomycetes in urban green space in subtropical China: Spatiotemporal patterns override forest type effects - Wen-Long Song; Di Lin; Min-Li Cai; Xia Chen; Qun Dai; Shuang-Lin Chen (Fungal Biology, 2025)

Preparation of W/W emulsion gels based on chitosan and carboxymethyl cellulose via associative phase separation - Jinfeng Zhao; Dehui Lin; Runguang Zhang; Di Wang; Aiqing Zhao; Honglei Tian; Xingbin Yang (Food Hydrocolloids, 2025)

Engineered honeysuckle extracellular vesicles loaded in ROS response hydrogel for inhibition of postoperative abdominal adhesion - Xiaolin Pan; Panyong Zhu; Yanwen Ding; Chenna Di; Zhe Yang; Haifeng Zhou; Chengwei Li; Lin Jin (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Multi-strategy for constructing S-scheme yolk-shell Ov-MnFe2O4@CuS bifunctional photoelectrocatalyst: detection and degradation of antibiotics - Bo Gao; Miao Zheng; Di Sun; Xinru Lin; Xue Feng; Yang Wang; Yuzhong Gao (Chemical Engineering Journal, 2025)

Regulation of discharge domains and dynamic processes in direct-current triboelectric nanogenerators - Bingzhe Jin; Yikui Gao; Di Liu; Lixia He; Zhihao Zhao; Zhong Lin Wang; Jie Wang (Chemical Engineering Journal, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

Strength Deterioration Characteristics of Soft and Hard Interbedded Rock Masses in Three Gorges Reservoir Area Induced by Wetting-Drying Cycles - Qiong Wu; Di Wang; Huiming Tang; Jintao Kang; Hongming Luo; Yuxin Liu; Shiyu Li; Bo Zhang; Zhiqi Liu; Zhiwei Lin (Journal of Earth Science, 2025)

Novel cyclometalated iridium(III) complex-based two-photon probe for visualizing mitochondrial nitroreductase and assessing treatment responses in sepsis-induced lung injury - Chaolong Liu; Peng Du; Lu Yuan; Lin Jiang; Jiabin Di; Yong Sun (Analytica Chimica Acta, 2025)

Optimizing cropland management to mitigate climate-induced nitrogen leakage risk in Chinese ecosystems - Di Zhao; Weijie Lin; Ke Yu; Zelin Huang; Chaopu Ti; Xiaoyuan Yan; Yongqiu Xia (Agricultural Systems, 2025)

Recent advances in bioassays for assessing the toxicity of environmental contaminants in effect-directed analysis - Yao Liu; Minjie Li; Qi-Lin Wan; Xun Wang; Monika Mortimer; Wen-Di Fang; Liang-Hong Guo (Journal of Environmental Sciences, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Prediction of asphalt rheological properties for paving and maintenance assistance using explainable machine learning - Fan Zhang; Augusto Cannone Falchetto; Di Wang; Zhenkun Li; Yuxuan Sun; Weiwei Lin (Fuel, 2025)

Interactive effects of warming and drought on soil organic carbon sequestration and methane uptake in straw and biochar amended soils: Mechanisms and global implications - Jitong Lin; Guopeng Liang; Marcela Hernández; Zhiyu Xu; Yinghao Xue; Renhua Sun; Yuanfeng Sun; Lulu Dai; Yanhong Lou; Haojie Feng; Hui Wang; Quangang Yang; et al. (Chemical Engineering Journal, 2025)

Plasma-Derived Small Extracellular Vesicles miR- 182 - 5p Is a Potential Biomarker for Diagnosing Major Depressive Disorder - Lin-Lin Zhu; Lian-Di Li; Xuan-Yu Lin; Jian Hu; Chun Wang; Yi-Jun Wang; Qi-Gang Zhou; Jing Zhang (Molecular Neurobiology, 2025)

Rheinheimera fenheensis sp. nov., Isolated from Fenhe River Basin, China - Xuan Shao; Yun-Lin Peng; Jin-Hang Guo; Zhao-Tong Chen; Hua-Ming Zhong; Di Meng; Hong-Jian Hou; Xi-Ying Zhang; Yong Zhao; Yi Li (Current Microbiology, 2025)

Pharmacokinetic study of Vibrio parahaemolyticus phage Фvp140 in Litopenaeus vannamei following oral administration - Di Fang; Laizhuang Jin; Qianhui Song; Xiong Zou; Lei Feng; Letian Li; Hui Zhang; Kun Hu; Mao Lin; Wenhong Fang (Aquaculture, 2025)

Assessing residents’ preference and willingness to pay for waste classification service modes: Evidence from discrete choice experiments in Beijing - Shufen Dai; Di Zhang; Chen Wang; Lin Zhu; Wei Gu (Waste Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A PLA2-responsive nanoagonist to boost immunotherapy via targeted release of lipid mediators in cold tumor microenvironment - Hui-Ping Wen; Meng-Die Zhu; Di Ning; Zhi-Gang Wang; Yusi Hu; Chuan-Ming Yu; Dai-Wen Pang; Shu-Lin Liu (Science Bulletin, 2025)

Ambient PM2.5 exposure, physical activity, and cardiovascular dysfunction: Analysis of CHARLS data and experimental study in mice - Hao Chang; Kun Pan; Xi Zhang; Zhonghua Lu; Yihui Wang; Di Liu; Yafen Lin; Yan Wu; Yi Lin; Qingyu Huang; Junchao Duan; Zhiwei Sun; et al. (Journal of Hazardous Materials, 2025)

Changes in soil organic carbon and its forms in recovering alpine meadows of various lengths in relation to altitude - Chunying Lin; Xilai Li; Huafang Sun; Xiaoxue Su; Hongmei Li; Rongna Liu; Chengyi Li; Yonghui Hou; Shizhen Zhu; Di Yu; Liyan Zhang; Jiexia Li; et al. (CATENA, 2025)

Environmental adversity, endoplasmic reticulum stress, and neurogenesis - Zuohui Zhang; Wen Wen; Di Hu; Hui Li; Hong Lin; Jia Luo (NeuroToxicology, 2025)

Applicability of three remote sensing based soil moisture variables for mapping soil organic matter in areas with different vegetation densities - Chenconghai Yang; Lin Yang; Lei Zhang; Feixue Shen; Di Fu; Shengfeng Li; Zhiqiang Chen; Chenghu Zhou (Journal of Hydrology, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Effortless rule: Effects of oversized microplastic management on lettuce growth and the dynamics of antibiotic resistance genes from fertilization to harvest - Jing-Yuan Chen; Lin-Jie Qin; Tiao Long; Rui-Ting Wu; Shi-Hua Niu; Shuo Liu; Wei-Kang Deng; Xin-Di Liao; Si-Cheng Xing (Journal of Hazardous Materials, 2025)

Protective effects of loquat leaf on tobacco-specific carcinogen NNK induced lung epithelial cell injury in vitro and in vivo by regulating miR-328-3p - Yingjie Wang; Zimu Liu; Fanyan Fang; Yapeng Liang; Bin Lin; Huiming Hua; Gang Chen; Di Zhou; Ning Li (Food Bioscience, 2025)

Characteristics of inland ship and the effect of combined diesel oxidation catalyst (DOC) and diesel particulate filter (DPF) aftertreatment system on their pollutant emissions - Thi-Hieu Le; Zhi-Ping Hsu; Cindy Soo Yun Tan; Cheng-Di Dong; Chitsan Lin; Tsun-Lirng Yang; Xuan-Thanh Bui; Lin-Chi Wang (Environmental Pollution, 2025)

Anti-swelling and ROS-scavenging nanofiber hydrogel to prevent postoperative abdominal adhesion - Wen Luo; Xiaolin Pan; Congling Ren; Taoxia Wang; Guiying Li; Lin Jin; Di Zhang (Chemical Engineering Journal, 2025)

Characteristics of orographic clouds and associated mechanisms in the Qilian Mountains, northeastern Tibetan Plateau based on FengYun-4A satellite TBB product - Yi Chang; Qianrong Ma; Peng Qi; Xueliang Guo; Dawei Lin; Lijun Guo; Di Di; Yang Zhao; Hui Wang; Tianyu Chen (Atmospheric Research, 2025)

Liquid–liquid phase separation in normal hematopoiesis and hematological diseases - Lexuan Lin; Fang He; Xu Jin; Xiaoru Zhang; Yue Li; Di Wang; Jingwei Wang; Lingyue Zheng; Haoze Song; Xu Zhu; Qimei Cheng; Yitong Zhao; et al. (Cell and Tissue Research, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Silencing ribosome biogenesis regulator 1 homolog (RRS1) inhibits angiogenesis and cisplatin resistance of lung cancer cells by activating ferroptosis mediated by p53 pathway - Ling Lin; Ying Zou; Di Zhang (Tissue and Cell, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Near-complete recovery of phosphorus from fresh human urine: Combining magnesium-air fuel cells with modified granular attapulgite - Lin-Jiang Zhong; Lin-Feng He; Hao-Ran Yang; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Ying Chen; Xuan Zhao; Hong Liu; Yuan Liu (Journal of Environmental Management, 2025)

Synthesis optimization for α-MnO2 with high benzene oxidation potential: Role of chemisorbed oxygen in the successive adsorption and oxidation of benzene - Di Zhang; Lin Cheng; Hao-Yu Lian; Xianliang Yi; Hao Zhou; Yang Liu (Journal of Environmental Chemical Engineering, 2025)

Enhancing anaerobic digestion of swine manure using microbial electrolysis cell and microaeration - Yanqiang Di; Wenxue Hou; Chunlin Bian; Tianlong Zheng; Benyi Xiao; Lin Li (Chemical Engineering Journal, 2025)

Combined Effects of Cadmium and Microplastics on the Wheat (Triticum aestivum L.) Plant-Soil System with the Partial Least Square Model: Phytotoxicity and Soil Properties - Yue Chen; Ding Qin; Fupeng Chen; Haitao Liu; Di Lin; Lantao Li (Journal of Soil Science and Plant Nutrition, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Soil surface properties and infiltration response to crust forming of a sandy loam and silt loam - Lin Lin; Patric Yemeli Lonla; Jaianth Vijayakumar; Muhammad Khizar Khan; Gemmina Di Emidio; Nick Krekelbergh; Ann Verdoodt; Wim Cornelis (Soil and Tillage Research, 2025)

Health risk assessment of dietary cadmium exposure based on cadmium bioavailability in food: Opportunities and challenges - Di Zhao; Guo-Bin Lin; Chenjing Liu; Albert L. Juhasz; Lena Q. Ma (Journal of Hazardous Materials, 2025)

Co-combustion reaction of corn stalk hydrochar and anthracite: Kinetics, mechanism and CO2 emission reduction - Wang Liang; Yihao Cui; Di Zhu; Yihan Chen; Yonghui Han; Lin Yue; Chunhe Jiang; Runsheng Xu; Xiaojun Ning; Jianliang Zhang; Chuan Wang; Guangwei Wang (Fuel, 2025)

Specifically targeted antimicrobial cyclic peptide to staphylococcal protein A for the treatment of S. aureus infection - Xiao-Ling Lei; Yong Li; Xue-Ting Cheng; Jie Zhuang; Fang Zhang; Xiao-Ting Xie; Lin-Fang Tan; Jin-Xuan Fan; Yuan-Di Zhao; Chuan-Liu Wu; Kai Cheng (Chemical Engineering Journal, 2025)

3D printing functional materials with extreme regulation of mechanical performances from hydrogel to engineering plastic - Di Liu; Yang Lyu; Zhengwei Lin; Zhongying Ji; Xiaolong Wang; Xinyan Shi (Chemical Engineering Journal, 2025)

Preparation and bioactivities of low-molecular weight fucoidans and fuco-oligosaccharides: A review - Hai-Di Liu; Dong-Yue Ma; Shan-Rui Shi; Shi-Lin Song; Wen-Lan Li; Xiao-Hui Qi; Shou-Dong Guo (Carbohydrate Polymers, 2025)

Plant polysaccharides and antioxidant benefits for exercise performance and gut health: from molecular pathways to clinic - Di Lin; Mohammad J. Rezaei (Molecular and Cellular Biochemistry, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Identification of salty and saltiness-enhancing peptides derived from phycocyanin in Arthrospira platensis - Lin Yuan; Qian Zhang; Di Liu; Wenzhu Zhao; Zhipeng Yu (Food Bioscience, 2025)

Thin basaltic regolith at the Chang'e-6 landing site - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Wei Yang; Yuyang He; Yi Chen; Roberto Bugiolacchi; Hengci Tian; Honglei Lin; Sen Hu (Earth and Planetary Science Letters, 2025)

Preferred crystal plane growth orientation induced by low-energy ions for highly reversible zinc anodes - Guanzhong Wang; Xiyan Bao; Xiaofang Wang; Xize Chen; Wei Lai; Di Wu; Chen Zhang; Lin Gao; Minglei Cao; Xingxing Li; Qin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Di-Wei Ma; Khalid Hassan Mohamed; Jian-Lin Hu; Chang-Qin Yin; Yu-Bin Wei; Xiao-Pan Chai; Qing-Bao Zhang; Lan-Chun Zhang; Jia Liu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2025)

How does the continuous changes in spring soil moisture over the Tibetan Plateau affect the summer precipitation in East China? - Di Ma; Xianhong Meng; Siqiong Luo; Lin Zhao; Zhaoguo Li; Yuanyuan Ma; Hao Chen; Lele Shu (Climate Dynamics, 2025)

Research on the coordination of a marine green fuel supply chain considering a cost-sharing contract and a revenue-sharing contract - Chang-yan Xu; Yi-qun Wang; Di-lin Yao; Si-yuan Qiu; Hui Li (Frontiers in Marine Science, 2025)
The marine green fuel supply chain is a crucial component in the development of green ports. Focusing on the issue of cooperative contracts between the port and green marine fuel supplier within the marine green fuel supply chain, first, a two-echelon marine green fuel supply chain optimization model consisting of a green marine fuel supplier and a port was constructed. Second, the changes in profits and decisions of a green marine fuel supplier and a port were compared under four scenarios: no contract, cost-sharing contract, revenue-sharing contract, and combined revenue-sharing + cost-sharing contract. Finally, the propositions were validated using numerical simulation methods. The research findings show that, in terms of revenue, the combined profits of a port and green marine fuel supplier under the combined revenue-sharing + cost-sharing contract exceeded those under the revenue-sharing contract alone. Regarding the sales price of marine green fuel and bunkering service quality, these factors peaked under the cost-sharing contract and were at their lowest under the revenue-sharing contract. An increase in the port’s investment proportion in marine green fuel bunkering service quality led to decreases in the bunkering volume, sales price, wholesale price, and bunkering service quality of marine green fuel under both the cost-sharing contract and the revenue-sharing + cost-sharing contract. Additionally, the higher proportion of revenue shared by the port with the green marine fuel supplier resulted in lower sales price, wholesale price, and bunkering service quality of green marine fuel under both the revenue-sharing contract and revenue-sharing + cost-sharing contract.

PWDViTNet: A lightweight early pine wilt disease detection model based on the fusion of ViT and CNN - Zhichao Chen; Haifeng Lin; Di Bai; Jingjing Qian; Hongping Zhou; Yunya Gao (Computers and Electronics in Agriculture, 2025)

On water entry/exit of free-fall lifeboats into regular waves: A computational fluid dynamics study - Ningge Fan; Gong Chen; Binyi Liang; Yingying Lin; Zhen Yue; Di Wang; Mengyan Zang; Shunhua Chen (Ocean Engineering, 2025)

Spatio-temporal characteristics and influencing factors of water quality in Xiangxi Bay under the operation of the three gorges reservoir - Aiping Jiang; Dongsheng Wang; Zhen Ning; Peng Li; Tao Xu; Boran Zhu; Qidong Peng; Tiantian Jin; Junqiang Lin; Di Zhang (Journal of Contaminant Hydrology, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Nondestructive detection of pungent and numbing compounds in spicy hotpot seasoning with hyperspectral imaging and machine learning - Di Zhang; Xu Chen; Zitao Lin; Minmin Lu; Wenhao Yang; Xiaoxia Sun; Maurizio Battino; Jiyong Shi; Xiaode Huang; Bolin Shi; Xiaobo Zou (Food Chemistry, 2025)

Efficacy and application potential of purified hydrocolloid coatings sprayed onto maize seeds subjected to anti-aging - Lin Zhang; Shi-Chao Yuan; Tai-Yue Wang; Xiang-Yang Wang; Xiao-Di Hao; Li-Ting Hao; Chen Shi (Environmental Research, 2025)

Hybrid physics and data-driven method for predicting existing tunnel lining deformation in twin tunnels construction - Xing-Tao Lin; Rui-Di Chen; Xiangsheng Chen; Hui Zeng (Computers and Geotechnics, 2025)

Progressive-composition-transformation-induced enhanced hyperthermia-based nanozyme towards long-lasting and complete therapy of cancer - Wenlong Zhang; Di Sun; Bin Yang; Jiaqi Liu; Yilin Yuan; Dezhuang Li; Yuliang Sun; Guoqiang Guan; Yanli Liu; Dapeng Wu; Hong Liao; Juntang Lin; et al. (Chemical Engineering Journal, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

Brems1 mutation induced tapetum deficiency leading to male sterility in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Chuanhong Liu; Lin Wang; Chong Tan; Di Zhao; Zhiyong Liu (Theoretical and Applied Genetics, 2025)

ETV5-Mediated Transcriptional Repression of DDIT4 Blocks Macrophage Pro-Inflammatory Activation in Diabetic Atherosclerosis - Lili Shi; Tingting Sun; Di Huo; Lin Geng; Chao Zhao; Wenbo Xia (Cardiovascular Toxicology, 2025)

Comparative analysis of embryonic development and growth performance among two mud crab species and their hybrids - Yang Zhao; Waqas Waqas; Wenxiao Cui; Shaopan Ye; Weifeng Gao; Qingyu Zhang; Zhen Lin; Di Zhu; Feng Lin; Mhd Ikhwanuddin; Hongyu Ma (Aquaculture, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Water-in-water emulsions stabilized by konjac glucomannan/tragacanth gum hydrogels for riboflavin delivery - Nitong Bu; Huanglong Lin; Di Zhang; Xianrui Chen; Pingping Tan; Yuanbo Zhong; Liying Huang; Jie Pang; Lin Wang; Ruojun Mu (Journal of Food Engineering, 2025)

Sensitive detection of Vibrio parahaemolyticus via a dual-recognition colorimetric biosensor comprising Cefe-PEG-MNPs and apt-Fe@PDA - Hongyong Lin; Tengyang Liao; Yaoyao Sang; Jin Mao; Yu Liu; Bin Zhang; Di Sun; Wei Jiang (Food Control, 2025)

Mechanisms of immune responses in Acanthopagrus latus to Streptococcus agalactiae infection revealed by transcriptomic analysis - Hong-Di Fan; Yuan-Ming Zhao; Min Liu; Xu Wang; Jia Lin; Wen Huang; Jiang-Hai Wang (Fish & Shellfish Immunology, 2025)

Overestimation of pore volume in high-TOC shales by low-temperature nitrogen adsorption: Phenomenon and cause analysis - Wenbin Jiang; Di Zhu; Chao Luo; Gaohui Cao; Lili Ji; Mian Lin; Zhuo Chen; Wenchao Dou; Kesu Zhong; Zhanhe Jia; Fang Hao (Chemical Engineering Journal, 2025)

Soil microbial diversity in boreal forests of China: A case study of the Altai Mountains with an emphasis on core microbiomes - Gu Rao; Wen-Long Song; Di Lin; Ya-Jing Chen; Shu-Zhen Yan; Shuang-Lin Chen (Applied Soil Ecology, 2025)

Flavaglines with anti-neuroinflammatory activity from Aglaia edulis (Roxb.) Wall. and structure revision of related flavaglines - Qianqian Yin; Gang Chen; Jinle Hao; Bin Lin; Qingqi Meng; Libin Xu; Di Zhou; Yue Hou; Ning Li (Phytochemistry, 2025)

New insights into the geological evolution history of Mare Fecunditatis - Zongyu Yue; Shujuan Sun; Jun Du; Sheng Gou; Kaichang Di; Yexin Wang; Yangting Lin; Xianhua Li; Fuyuan Wu (Icarus, 2025)

Facile synthesis of magnetic ionic covalent organic framework and dispersive magnetic solid phase extraction of aromatic amino acid oxidation products in thermally processed foods - Yujie Yang; Wenrui Li; Di Wu; Yongning Wu; Lin Li; Guoliang Li (Food Chemistry, 2025)

Regulatory effects and mechanism of different selenium species on cadmium accumulation in Triticum aestivum L. (microbial response, gene expression and element accumulation) - Xuerong Di; Rui Jing; Xu Qin; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Environmental Research, 2025)

Mesoporous dual-atom nanozyme induced cuproptosis and apoptosis for boosting immunogenic cell death along with reprogramming tumor immune-suppressive microenvironment - Yunhao Wang; Lei Ding; Ziguo Lin; Baolong Li; Di Hu; Shichen Zhang; Shujun Zhou; Yuxiang Ning; Fei Xin; Yunfei Ying; Fukai Zhu; Peiyuan Wang; et al. (Chemical Engineering Journal, 2025)

A crazy trio in Parkinson's disease: metabolism alteration, α-synuclein aggregation, and oxidative stress - Sheng Li; Yanbing Liu; Sen Lu; Jiayi Xu; Xiaokun Liu; Di Yang; Yuxuan Yang; Lin Hou; Ning Li (Molecular and Cellular Biochemistry, 2025)

Soil properties, climate, and topography jointly determine plant community characteristics in marsh wetlands - Lin Yuan; Jingzhi Wang; Rong Liu; Yuqi Tang; Di Wu; Ri Jin; Weihong Zhu (Journal of Plant Research, 2025)

Evaluating the impacts of converting grain to vegetable fields on nitrate transport in the deep vadose zone of the North China Plain - Meiying Liu; Leilei Min; Lin Wu; Yucui Zhang; Yongqing Qi; Shiqin Wang; Binbin Liu; Di Geng; Yanjun Shen (Journal of Geographical Sciences, 2025)

Trajectory optimization of spacecraft autonomous far-distance rapid rendezvous based on deep reinforcement learning - Peng Di; Ye Yao; Zheng Lin; Zengshan Yin (Advances in Space Research, 2025)

Prediction of Drug-Drug Interactions for Highly Plasma Protein Bound Compounds - David Tess; Makayla Harrison; Jian Lin; Rui Li; Li Di (The AAPS Journal, 2024)

Egg production monitoring in commercial laying cages via the StrongSort-EGG tracking-by-detection model - Rui Wu; Pengguang He; Yefan He; Jun Dou; Mengzui Di; Shupeng He; Khawar Hayat; Yi Zhou; Lin Yu; Jinming Pan; Hongjian Lin (Computers and Electronics in Agriculture, 2024)

Characterizing persistent organic pollutants in seawater at a multifunctional international harbor influenced by industrial riverbank activities - Fefi Eka Wardiani; Cheng-Di Dong; Chiu-Wen Chen; Ta-Kang Liu; Zhi-Ping Hsu; Su Shiung Lam; Lin-Chi Wang (Marine Pollution Bulletin, 2024)

Response of aerobic granular sludge to salinity fluctuations in formation, stability and microbial community structures - Jie Xu; Shichang Liu; Jiazhong Zhou; Lin Li; Xuejun Bi; Wenjie Han; Di Wu (Science of The Total Environment, 2024)

Asymmetrical distribution of 1–20 km craters on the Moon - Chenxu Zhao; Zongyu Yue; Kaichang Di; Yutong Jia; Wing-Huen Ip; Yangting Lin; Bo Wu; Biao Wang; Bin Xie (Planetary and Space Science, 2024)

A phenological-knowledge-independent method for automatic paddy rice mapping with time series of polarimetric SAR images - Suya Lin; Zhixin Qi; Xia Li; Hui Zhang; Qianwen Lv; Di Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Complex basalt evolution in the Chang'e-6 landing area - Sheng Gou; Zongyu Yue; Yangting Lin; Kaichang Di; Patrick C. Pinet; Roberto Bugiolacchi; Yuyang He; Wei Yang; Honglei Lin; Hengci Tian; Sen Hu (Earth and Planetary Science Letters, 2024)

Construction of epoxy composites with double alternating “rigid-flexible” structures: Curing kinetics and thermal/mechanical properties - Mengyu Liang; Xing Liu; Di Liu; Xiaopeng Li; Ting-Ting Li; Jia-Horng Lin; Boyan Chang; Jie Chen (Chemical Engineering Journal, 2024)

Contact-electro-luminescence triggered by triboelectric charge - Chong Xu; Shaoxin Li; Zhe Yang; Morten Willatzen; Zhong Lin Wang; Di Wei (Chemical Engineering Journal, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

Hesperidin and 5, 7-dimethoxycoumarin act as markers in the chemotaxonomy of Citrus medica L. var. sarcodactylis Swingle and Citrus medica L. - Di Wu; Miao-Miao Zhang; Hong-Ping Long; Xiao-Yuan Lin; Kai Liu (Biochemical Systematics and Ecology, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

In-situ synthesis of 2D nanozymes-coated cellulose nanofibers on paper-based chips for portable detection of biothiols - Chao Di; Yiwei Zhang; Lian Xue; Wenyi Zeng; Tengteng Wang; Yiwei Lin; Peng Chen; Xiaojun Feng; Wei Du; Bi-Feng Liu (Analytica Chimica Acta, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Tracking paddy rice acreage, flooding impacts, and mitigations during El Niño flooding events using Sentinel-1/2 imagery and cloud computing - Ruoqi Liu; Jinwei Dong; Yong Ge; Hui Lin; Xianghong Che; Yuanyuan Di; Xi Chen; Shuhua Qi; Mingjun Ding; Xiangming Xiao; Geli Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Relationships between water quality of a long-distance inter-basin water diversion project and air pollution emissions along the canal: Distributions, lag effects, and nonlinear responses - Xizhi Nong; Kunting Luo; Minzhi Lin; Lihua Chen; Di Long (Environmental Pollution, 2024)

Fiber-based model for rectangular/square concrete-filled steel tubular columns under arbitrary end moment ratios considering member imperfection - Xi-Feng Yan; Siqi Lin; Di Yang; Yan-Gang Zhao (Engineering Structures, 2024)

Oceanic response to tropical cyclone in the northern South China Sea observed by underwater gliders during 2018 and 2020 - Yanfeng Zhang; Han Zhang; Xiaodong Tang; Shaoqiong Yang; Yanhui Wang; Xiayan Lin; Di Tian; Dake Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Microbial groups containing alkaline phosphatase accelerate soil phosphate mineralization in two soil patterns with contrasting pH levels - Hui Li; Jitong Lin; Qi Shao; Beibei Zhang; Yunting Wang; Linke Wang; Haojie Feng; Yanhong Lou; Hui Wang; Quangang Yang; Zhongchen Yang; Hongjie Di; et al. (Journal of Soils and Sediments, 2024)

Exosomal miR-21-5p derived from endometrial stromal cells promotes angiogenesis by targeting TIMP3 in ovarian endometrial cysts - Liyuan Sun; Yan Cheng; Jing Wang; Di Wu; Lin Yuan; Xiaoyu Wei; Yan Li; Jie Gao; Guangmei Zhang (Journal of Molecular Medicine, 2024)

Advances in perfluoro-alkylated compounds (PFAS) detection in seafood and marine environments: A comprehensive review on analytical techniques and global regulations - Prasath Ramasamy Chandrasekaran; Jeganathan Chinnadurai; Yee Cheng Lim; Chiu-Wen Chen; Pei-Chien Tsai; Po-Chin Huang; Mohsen Gavahian; Gangadhar Andaluri; Cheng-Di Dong; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Environmental Geochemistry and Health, 2024)

A nanopore-based label-free CRISPR/Cas12a system for portable and ultrasensitive detection of zearalenone - Ziye Pei; Zhuoqun Su; Jianing Chen; Wenrui Li; Di Wu; Lin Li; Yongning Wu; Guoliang Li (Analytica Chimica Acta, 2024)

Advanced electrochemical membrane technologies for near-complete resource recovery and zero-discharge of urine: Performance optimization and evaluation - Hao-Ran Yang; Yuan Liu; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Chuan Wang; Hong Liu (Water Research, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Sustainable double-synergistic silver-hydroxyapatite composite catalyst derived from fish bones for efficient disinfection of Vibrio parahaemolyticus - Di Sun; Tengyang Liao; Hongyong Lin; Yaoyao Sang; Yu Liu; Qingbao Ma; Zhongjie Yu; Bin Zhang; Wei Jiang (Food Chemistry, 2024)

Comprehensive insights into the refractory melanoidins production from structural extracellular polymeric substances via thermal hydrolysis pretreatment and the inhibition on anaerobic fermentation - Si-Di Hong; Shuai Wang; Xiao-Fei Yang; Xing-Chen Huang; Jia-Xiang Xiao; Wen-Xuan Wang; Jiahuan Tang; Hao Lin; Raymond Jianxiong Zeng; Kun Dai; Fang Zhang (Chemical Engineering Journal, 2024)

Spatial–temporal distribution characteristics of surface water pollutants and their potential sources in Ngari, China - Yubing Zhu; Xiao Sun; Lin Shi; Di Zhang; Meizhen Wu; Liming Chai; Jinfeng Zhao (Environmental Geochemistry and Health, 2024)

RETRACTED ARTICLE: TFAP2C Activates CST1 Transcription to Facilitate Breast Cancer Progression and Suppress Ferroptosis - Lin Yuan; Di Zhou; Weiwen Li; Jianhua Guan; Junda Li; Bo Xu (Biochemical Genetics, 2024)

Hormetic responses to cadmium exposure in wheat seedlings: insights into morphological, physiological, and biochemical adaptations - Qiujuan Jiao; Gezi Li; Lantao Li; Di Lin; Zhengyang Xu; Lina Fan; Jingjing Zhang; Fengmin Shen; Shiliang Liu; Chandra Shekhar Seth; Haitao Liu (Environmental Science and Pollution Research, 2024)

Pore structure and mineral composition characteristics of coal slime before and after ashing and the effects on CO2 adsorption - Xiangguo Kong; Jie Hu; Yuchu Cai; Xi Lin; Yuxuan Zhou; Di He; Pengfei Ji (Environmental Science and Pollution Research, 2024)

Vibration reduction and efficiency enhancement effects of twisted rudders in submarines under small rudder angle conditions - Di Zhang; Jin-ming Ye; Wan-li Yang; Yuan-run Wu; Jian-lin Shou (Ocean Engineering, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

Effects of pore characteristics on CO2 adsorption performance of coal slime with different metamorphic degrees - Xiangguo Kong; Xi Lin; Yuchu Cai; Liang Chen; Jie Hu; Yuxuan Zhou; Pengfei Ji; Di He (Journal of Environmental Management, 2024)

Unlocking synergies of drawdown operation: Multi-objective optimization of reservoir emergency storage capacity - Shufei Li; Di Zhu; Fanqi Lin; Jun Xia; Yanlai Zhou; Fi-John Chang; Chong-Yu Xu (Journal of Environmental Management, 2024)

Ocean acidification alters microeukaryotic and bacterial food web interactions in a eutrophic subtropical mesocosm - Ruiping Huang; Ping Zhang; Xu Zhang; Shouchang Chen; Jiazhen Sun; Xiaowen Jiang; Di Zhang; He Li; Xiangqi Yi; Liming Qu; Tifeng Wang; Kunshan Gao; et al. (Environmental Research, 2024)

Perovskite intermediate phase FAPbBr3·DMSO assisted in-situ growth of FAPbBr3 polycrystalline wafer for X-ray detection and imaging - Dan Liu; Wei Jiang; Siyin Dong; Haipeng Di; Haibin Li; Zhenning Xing; Hongbing Wang; Jiwei Ren; Xiaojia Zheng; Lin Lei; Yiying Zhao (Chemical Engineering Journal, 2024)

Three-dimensional mixed-valence polyoxovanadates@polyaniline architecture towards high-performance rechargeable aqueous zinc-ion batteries cathode - Xue-Wei Liang; Yu-Ying Yang; Wen-Fei Di; Si-Yu Chen; Rui Zhang; Jisong Hu; Dunmin Lin; Yu Huo (Chemical Engineering Journal, 2024)

Global quantitative synthesis on the patterns and drivers of funneling ratio and enrichment ratio for stemflow - Meng-Di Wu; Zhi-Yun Jiang; Xiao Yang; Buerlan Yeerbolati; Lin Huang; Ying-Yin Zhong; Han-Wen Zhang; Xiao-Yan Li (CATENA, 2024)

Estimating visibility and understanding factors influencing its variations at Bangkok airport using machine learning and a game theory–based approach - Nishit Aman; Sirima Panyametheekul; Sumridh Sudhibrabha; Ittipol Pawarmart; Di Xian; Ling Gao; Lin Tian; Kasemsan Manomaiphiboon; Yangjun Wang (Environmental Science and Pollution Research, 2024)

Global associations between long-term exposure to PM2.5 constituents and health: A systematic review and meta-analysis of cohort studies - Sujuan Chen; Di Liu; Lin Huang; Cui Guo; Xiaoke Gao; Zhiwei Xu; Zhou Yang; Yu Chen; Mengmeng Li; Jun Yang (Journal of Hazardous Materials, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

EVA1A reverses lenvatinib resistance in hepatocellular carcinoma through regulating PI3K/AKT/p53 signaling axis - Xiaokun Liu; Xiao Gao; Yuling Yang; Di Yang; Qingming Guo; Lianhui Li; Shunlong Liu; Wanxin Cong; Sen Lu; Lin Hou; Bin Wang; Ning Li (Apoptosis, 2024)

Neuroprotective and vasoprotective effects of herb pair of Zhiqiao-Danggui in ischemic stroke uncovered by LC-MS/MS-based metabolomics approach - Benxing Yao; Di Xu; Qing Wang; Lin Liu; Ziyun Hu; Wenya Liu; Qi Zheng; Huihui Meng; Ran Xiao; Qian Xu; Yudie Hu; Junsong Wang (Metabolic Brain Disease, 2024)

Differential expression of ADRB1 causes different responses to norepinephrine in adipocytes of Duroc-Landrace-Yorkshire pigs and min pigs - Yuelei Zhao; Xuexin Li; Wensai Yu; Weimin Lin; Wei Wei; Lifan Zhang; Di Liu; Hong Ma; Jie Chen (Journal of Thermal Biology, 2024)

The role and transcriptomic mechanism of cell wall in the mutual antagonized effects between selenium nanoparticles and cadmium in wheat - Xuerong Di; Rui Jing; Xu Qin; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Journal of Hazardous Materials, 2024)

Regulation of gene expression in the secondary metabolic synthesis pathway of Lonicera japonica Flos by yeast polysaccharides - Xu-peng Gu; Lin-lin Yang; Da-ming Qi; Di Zhang; Tian-liang Liu; Cheng-ming Dong (Physiology and Molecular Biology of Plants, 2024)

Spatiotemporal estimation of hourly PM2.5 using AOD derived from geostationary satellite Fengyun-4A and machine learning models for Greater Bangkok - Nishit Aman; Kasemsan Manomaiphiboon; Di Xian; Ling Gao; Lin Tian; Natchanok Pala-En; Yangjun Wang; Komsilp Wangyao (Air Quality, Atmosphere & Health, 2024)

A study on an accurate modeling for distinguishing nitrogen, phosphorous and potassium status in summer maize using in situ canopy hyperspectral data - Di Lin; Yue Chen; Yongliang Qiao; Ding Qin; Yuhong Miao; Kai Sheng; Lantao Li; Yilun Wang (Computers and Electronics in Agriculture, 2024)

Coating seeds with biopolymers extracted from waste-activated sludge - Chen Shi; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Shi-Ming Su; Zhongfang Lei; Xiao-Di Hao (Sustainable Chemistry and Pharmacy, 2024)

DPABINet: A toolbox for brain network and graph theoretical analyses - Chao-Gan Yan; Xin-Di Wang; Bin Lu; Zhao-Yu Deng; Qing-Lin Gao (Science Bulletin, 2024)

Transcriptomic mechanism revealed IbGST4 and IbGST2 genes response to low-temperature stress in sweet potatoes - Wei-Sheng Zhao; Long-Fei Yan; Kang-Di Hu; Zhi-Lin Zhou; Si-Qi Wang; Le-Ying Yan; Fan Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2024)

North Lhasa terrane in the Precambrian originated from Western Australia - Changsheng Yu; Ming Wang; Di Shen; Mengxian Lin; Shengshuo Zhang; Rui Yang; Danzeng Quewang (Precambrian Research, 2024)

Development and comprehensive SBSE-GC/Q-TOF-MS analysis optimization, comparison, and evaluation of different mulberry varieties volatile flavor - Di Ma; Tianbao Lin; Huiyu Zhao; Yougui Li; Xinquan Wang; Shanshan Di; Zhenzhen Liu; Mingqi Liu; Peipei Qi; Suling Zhang; Rui Jiao (Food Chemistry, 2024)

Density and volume of adsorbed methane in key applications for in-situ gas content: Insights from molecular simulation - TengFei Jia; Songhang Zhang; Shuheng Tang; Di Xin; Shouren Zhang; Bingjie Wang; Qian Zhang; Ke Zhang; Donglin Lin; Wenfu Yang (Chemical Engineering Journal, 2024)

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

Comparative study on the nutrient recovery from source-separated urine using magnesium-air fuel cell in different operating modes - Lin-Feng He; Shu-Jie Hu; Di Wu; Meng-Yue Zhang; Hong Liu; Yuan Liu (Process Safety and Environmental Protection, 2024)

Rapid determination of geographical authenticity and pungency intensity of the red Sichuan pepper (Zanthoxylum bungeanum) using differential pulse voltammetry and machine learning algorithms - Di Zhang; Zitao Lin; Lilei Xuan; Minmin Lu; Bolin Shi; Jiyong Shi; Fatao He; Maurizio Battino; Lei Zhao; Xiaobo Zou (Food Chemistry, 2024)

Construction of Ni3S4@ZIS@C3N5 photocatalyst with type II and Z-type heterojunctions by self-assembly for efficient photocatalytic hydrogen evolution - Huixiang Yan; Wei Li; Huixing Yang; Yongzhuo Yu; Chaoyu Lv; Linlin Hou; Wenxu Zhang; Di Lin; Shichao Jiao (Environmental Research, 2024)

Tree barriers height information extraction under power line based on watershed segmentation and local maximum algorithm - Yan Li; Lv Zhou; Xue Lin Wen; Tai Ying Wu; Mian Lan; Di Zhang; Yi Zhan Zhao; Peng De Lai (International Journal of Remote Sensing, 2024)

Preparing a heavy-metal adsorbent based on alginate-like extracellular polymers from conventional activated sludge via polyethyleneimine grafting - Chen Shi; Run-Gen Zeng; Shi-Chao Yuan; Lin Zhang; Xiang-Yang Wang; Li-Ting Hao; Xiao-Di Hao; Nan Zhang; Yuan-Yuan Wu (Sustainable Chemistry and Pharmacy, 2024)

Chemical profile of the roots of Clausena lansium and their inhibitory effects of the over-activation in BV-2 microglial cells - Yingjie Wang; Gang Chen; Di Zhou; Libin Xu; Qingqi Meng; Bin Lin; Jinle Hao; Fuxin Sun; Yue Hou; Ning Li (Phytochemistry, 2024)

Impact of ethanol extract of propolis on heat-induced egg white protein gels: Formation and properties - Man Zhang; Lin Mei; Yating Wu; Guoguo Jin; Di Bao (Food Hydrocolloids, 2024)

High-Performance low-k Poly(dicyclopentadiene)-POSS nanocomposites achieved by frontal polymerization - Dai-Lin Zhou; Jian Wang; Hongwei Bai; Di Han; Qiang Fu (Chemical Engineering Journal, 2024)

Cellulose nanofibers embedded chitosan/tannin hydrogel with high antibacterial activity and hemostatic ability for drug-resistant bacterial infected wound healing - Dangwei Li; Xiangyang Dong; Xia Liu; Heng Lin; Di Yang; Xiaowen Shi; Chaoji Chen; Fenghua Tao; Linbin Jiang; Hongbing Deng (Carbohydrate Polymers, 2024)

FireViTNet: A hybrid model integrating ViT and CNNs for forest fire segmentation - Guodong Wang; Di Bai; Haifeng Lin; Hongping Zhou; Jingjing Qian (Computers and Electronics in Agriculture, 2024)

New discovery of extremely high adsorption of environmental DNA on cuttlefish bone pyrolysis derivative via large pore structure and carbon film - Lin Shi; Di Zhang; Mingyi Yang; Fangfang Li; Jinfeng Zhao; Zhaohui He; Yangwei Bai (Waste Management, 2024)

Prediction of molecular-specific mutagenic alerts and related mechanisms of chemicals by a convolutional neural network (CNN) model based on SMILES split - Chao Chen; Zhengliang Huang; Xuyan Zou; Sheng Li; Di Zhang; Shou-Lin Wang (Science of The Total Environment, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Geothermal reservoir characteristics of SYYD-1 well and energy efficiency analysis after geothermal transformation - Xiao Li; Lin Chen; Xiaomin Zhu; Jizhong Du; Xiaoguang Wang; Jianguo Yang; Di Wang; Xiaodong Guo; Qiang Liu; Hailong Wu (Geothermics, 2024)

A versatile AIE probe with two cross-talk-free emissions for dual detection of SO2 and viscosity and its application in food and biological imaging - Di Zhang; Min Wang; Man Li; Lin Liu; Ran Duan; Nana Xue; He Chen; Lijun Shang; Tieliang Wang; Xujin Wu; Junfeng Zhang (Food Chemistry, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

Correction to: A Chinese Family with Digenic TBP/STUB1 Spinocerebellar Ataxia - Lili Liu; Juanjuan Chen; Guogao Zhang; Zhijian Lin; Di Chen; Jun Hu (The Cerebellum, 2024)

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

A Chinese Family with Digenic TBP/STUB1 Spinocerebellar Ataxia - Lili Liu; Juanjuan Chen; Guogao Zhang; Zhijian Lin; Di Chen; Jun Hu (The Cerebellum, 2024)

The impact of sea ice melt on the evolution of surface pCO2 in a polar ocean basin - Wei Yang; Yu Zhao; Yingxu Wu; Zijie Chen; Xiang Gao; Hongmei Lin; Zhangxian Ouyang; Weijun Cai; Liqi Chen; Di Qi (Frontiers in Marine Science, 2024)
The strong CO 2 sink in Arctic Ocean plays a significant role in the global carbon budget. As a high-latitude oceanic ecosystem, the features of sea surface p CO 2 and air-sea CO 2 flux are significantly influenced by sea ice melt; however, our understanding of p CO 2 evolution during sea ice melt remains limited. In this study, we investigate the dynamics of p CO 2 during the progression of sea ice melt in the western Arctic Ocean based on data from two cruises conducted in 2010 and 2012. Our findings reveal substantial spatiotemporal variability in surface p CO 2 on the Chukchi Sea shelf and Canada Basin, with a boundary along the shelf breaks at depths of 250-500 m isobaths. On the Chukchi Sea shelf, strong biological consumption dominates p CO 2 variability. Moreover, in Canada Basin, the p CO 2 dynamics are modulated by various processes. During the active sea ice melt stage before sea ice concentration decreases to 15%, biological production through photosynthetic processes and dilution of ice melt water lead to a reduction in DIC concentration and subsequent decline in p CO 2 . Further, these effects are counteracted by the air-sea CO 2 exchange at the sea surface which tends to increase seawater DIC and subsequently elevate surface p CO 2 . Compared to the p CO 2 reduction resulting from biological production and dilution effects, the contribution of air-sea CO 2 exchange is significantly lower. The combined effects of these factors have a significant impact on reducing p CO 2 during this stage. Conversely, during the post sea ice melt stage, an increase in p CO 2 resulting from high temperatures and air-sea CO 2 exchange outweighs its decrease caused by biological production. Their combined effects result in a prevailing increase in sea surface p CO 2 . We argue that enhanced air-sea CO 2 uptake under high wind speeds also contributes to the high sea surface p CO 2 observed in 2012, during both active sea ice melt stage and post sea ice melt stage. The present study reports, for the first time, the carbonate dynamics and p CO 2 controlling processes during the active sea ice melt stage. These findings have implications for accurate estimation of air-sea CO 2 fluxes and improved modeling simulations within the Arctic Ocean.

Phthalate esters and nonylphenol concentrations correspond with microplastic distribution in anthropogenically polluted river sediments - Ming-Huang Wang; Chih-Feng Chen; Frank Paolo Jay B. Albarico; Shan-Lu Lin; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2024)

A fluorescent dual-emitting platform for fluorescent “turn-on” ratiometric detection of ascorbic acid in beverages utilizing luminol-embedded iron-based metal–organic frameworks - Kanglin Pei; Jianyang Xu; Di Wu; Lin Qi; Lingyan Ma; Renwen Zhang; Wenjing Qi (Food Chemistry, 2024)

Catalytic PMS oxidation universality of CuFe2O4/MnO2 heterojunctions at multiple application scenarios - Di Song; Zixuan Zheng; Zhenzhou Wang; Mengyuan Zhao; Lin Ding; Qian Zhang; Fang Deng (Environmental Research, 2024)

Elucidating the function and potential inhibitory impact of monovalent cations on assessing the biodegradability of organic substrates in biochemical sulfide potential (BSP) assay - Lin Chen; Di Wu; Guanghao Chen (Bioresource Technology, 2024)

Differential roles of anthropogenic CO2 in mediating seasonal amplitudes of ocean acidification metrics over a coastal coral habitat - Xu Dong; Di Qi; Baohong Chen; Yingxu Wu; Xinqing Zheng; Hui Lin (Journal of Marine Systems, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Multi-Risk Interaction Analysis of Cascade Hydropower Stations Based on System Dynamics Simulation - Boran Zhu; Junqiang Lin; Yi Liu; Di Zhang; Qidong Peng; Yufeng Ren; Jiejie Chen; Yi Xu (Water Resources Management, 2024)

Observed oceanic response to Tropical Cyclone Amphan (2020) from a subsurface mooring in the Bay of Bengal - Yingyu Peng; Di Tian; Feng Zhou; Han Zhang; Xiao Ma; Dingyong Zeng; Qicheng Meng; Beifeng Zhou; Ruijie Ye; Yeqing Chen; Feilong Lin; Zhentao Hu; et al. (Progress in Oceanography, 2023)

Chitosan composite films based on tea seed oil nano-microcapsules: Antibacterial, antioxidant and physicochemical properties - Qiuya Ji; Zhou Jin; Wanlu Ding; Yating Wu; Chunjie Liu; Kang Yu; Nannan Zhang; Guoguo Jin; Peiran Lu; Di Bao; Lin Mei (Food Packaging and Shelf Life, 2023)

Bioleaching of Silicon from Fly Ash by Co-culture of Silicate Bacteria and Fungi - Yanzhu Lin; Shida Li; Xuefeng Li; Hanrui Lin; Ningfei Lei; Di Wu; Jin Tong; Hongguan Xie (Water, Air, & Soil Pollution, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Influencing Factors and New Reference Intervals of Adult Thyroid Volume in Iodine-Sufficient Areas of China - Zheyu Lin; Cihang Lu; Di Teng; Ying Sun; Tingting Liu; Yongze Li; Zhongyan Shan; Weiping Teng (Biological Trace Element Research, 2023)
The diagnosis of goiter is based on the thyroid volume measured by ultrasound in which iodine plays an important role. The purpose of this study was to evaluate the factors that affect thyroid volume and update the reference range of thyroid volume to provide a new basis for the diagnosis and treatment of goiter. A study population from mainland China was evaluated in the Thyroid disorders, Iodine status and Diabetes Epidemiological (TIDE) study. Thyroid size was measured by ultrasound, and thyroid volume was calculated. A quantile regression model was used to analyze the influence of related factors on the thyroid volume at each percentile. The median urinary iodine concentration (UIC) was 185.54 μg/l. The quantile regression model suggested that body surface area (BSA) and thyroid-stimulating hormone (TSH) were positive and negative factors for thyroid volume, respectively ( p < 0.01). Excess iodine reduces the median and lower limits of thyroid volume. In iodine-sufficient areas, smoking is no longer a risk factor. The reference value range of thyroid volume stratified by sex was 3.92–19.06 ml for males and 3.1–16.17 ml for females. The maximum reference ranges for stratification by sex and BSA were 4.25–20.98 ml for men and 3.44–18.31 ml for women. The iodine nutrition level of the population in mainland China is sufficient. Iodine has the potential to alter the effect of certain factors on thyroid volume and effect is not regional. The new reference interval of adult thyroid volume based on sex and BSA has been updated, which can be used as a reliable reference for updating the diagnostic criteria of endemic goiter.

Investigation of Potential Crucial Genes and Key Pathways in Keratoconus: An Analysis of Gene Expression Omnibus Data - Di Hu; Zenan Lin; Pan Li; Zhehuan Zhang; Junhong Jiang; Chenhao Yang (Biochemical Genetics, 2023)

Spatial symmetry and contrasting controls of surface pH and aragonite saturation state in the western North Pacific - Cheng-long Li; Yingxu Wu; Kui Chen; Hongmei Lin; Liqi Chen; Di Qi (Frontiers in Marine Science, 2023)
Oceanic uptake of anthropogenic CO 2 causes a decrease in seawater pH and aragonite saturation state (Ω arag ), a process known as ocean acidification (OA). The western North Pacific is a hotspot for anthropogenic CO 2 sinks; however, the spatiotemporal variability of pH and Ω arag and their controlling mechanisms remain unexplored. In this study, we provide high-frequency and high-precision underway measurements of sea surface p CO 2 and pH to investigate the distribution and drivers of OA metrics across different hydrochemical gradients in the western North Pacific in late spring 2018, a season with the highest primary production in the year. Our results show that the surface pH reached near air-sea equilibrium in the subtropical zone but gradually increased northward across the Kuroshio Recirculation (KR) zone and peaked in the Kuroshio Extension (KE) zone. We found that sea surface temperature played the most prominent role in regulating pH, which was also counteracted by the effects of air–sea gas exchange and vertical mixing. In contrast, the distribution of Ω arag largely mirrored the pH and was governed by air–sea gas exchange and vertical mixing, the effects of which on Ω arag were enhanced by temperature. Biological activity thrived in the KE zone to increase both pH and Ω arag , which further reinforced the latitudinal pattern of pH, but weakened that of Ω arag . These findings are based on direct in situ measurements of pH and improve our understanding of the spatiotemporal variability of OA metrics in the western North Pacific region.

Mechanical damages and packaging methods along the fresh fruit supply chain: A review - Menghua Lin; Olaniyi Amos Fawole; Wouter Saeys; Di Wu; Jun Wang; Umezuruike Linus Opara; Bart Nicolai; Kunsong Chen (Critical Reviews in Food Science and Nutrition, 2023)

Transcranial Alternating Current Stimulation in a Patient with Ataxia-Ocular Apraxia 2: a Case Report - Xiao-Ping Cheng; Wen-Hui Yu; Xia Liu; Wei Lin; Zhao-Di Wang; Xi-Chen Wang; Jun Ni; Nai-Qing Cai; Xin-Yuan Chen (The Cerebellum, 2023)

Transcriptome analysis reveals the molecular mechanism of different forms of selenium in reducing cadmium uptake and accumulation in wheat seedlings - Xuerong Di; Rui Jing; Xu Qin; Yihua Wei; Xuefeng Liang; Lin Wang; Yingming Xu; Yuebing Sun; Qingqing Huang (Chemosphere, 2023)

Revealing maleic acid role in the preparation of α-hemihydrate gypsum from titanium gypsum through experiments and DFT calculations - Jingwei Du; Lin Tian; Manfu Qi; Chen Zhang; Hongfeng Di; Xiao Zhi; Jianping Zhu (Science of The Total Environment, 2023)

Distribution, assembly, and interactions of soil microorganisms in the bright coniferous forest area of China's cold temperate zone - Gu Rao; Shu-Zhen Yan; Wen-Long Song; Di Lin; Ya-Jing Chen; Shuang-Lin Chen (Science of The Total Environment, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Exploring a multi-objective optimization operation model of water projects for boosting synergies and water quality improvement in big river systems - Di Zhu; Yanlai Zhou; Shenglian Guo; Fi-John Chang; Kangling Lin; Zhimin Deng (Journal of Environmental Management, 2023)

Oxidation of Sb(III) by Shewanella species with the assistance of extracellular organic matter - Kai-Li Wang; Di Min; Guan-Lin Chen; Dong-Feng Liu; Han-Qing Yu (Environmental Research, 2023)

The role of a novel coating of SFRCR-ECC in enhancing the fire performance of CFST columns: Development, characteristic and ISO-834 standard fire test - Yan Xiong; Kairen Lin; Di Wu; Yuhong Ling; Solomon Tesfamariam (Engineering Structures, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

Highly effective synthesis of 5-hydroxymethylfurfural from lignocellulosic biomass over a green and one-pot reaction in biphasic system - Quang Tam Huynh; Chong-Ting Zhong; Qing Huang; Yuan-Chung Lin; Ku-Fan Chen; Chien-Sen Liao; Cheng-Di Dong; Ken-Lin Chang (Bioresource Technology, 2023)

Progresses and prospects of impact crater studies - Zongyu Yue; Ke Shi; Kaichang Di; Yangting Lin; Sheng Gou (Science China Earth Sciences, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Cyberinformatics tool for in-season crop-specific land cover monitoring: Design, implementation, and applications of iCrop - Chen Zhang; Liping Di; Li Lin; Haoteng Zhao; Hui Li; Anna Yang; Liying Guo; Zhengwei Yang (Computers and Electronics in Agriculture, 2023)

On the dissolution paths and formation mechanisms of paleokarst reservoirs: Constraints from reactive transport modeling - Ying Xiong; Xiucheng Tan; Bo Liu; Zhengmeng Hou; Jiashun Luo; Lin Wu; Feifan Lu; Di Xiao (Marine and Petroleum Geology, 2023)

Geodynamic controls on the Paleo-Asian oceanic plate evolution: Constraints from Paleozoic intrusive suites along the northern margin of the North China Block - Jialiang Li; Chen Wu; Lin Cheng; Hao Yang; Di-Cheng Zhu; Jingao Liu (Lithos, 2023)

Non-target and target analysis to identify and characterize thiophenes in soil from an abandoned coking plant - Qiaofeng Ai; Lirong Gao; Di Huang; Jing Yang; Qiang Fu; Xuan Zheng; Yang Liu; Lin Qiao; Jiyuan Weng; Minghui Zheng (Journal of Hazardous Materials, 2023)

Integrated MOVES model and machine learning method for prediction of CO2 and NO from light-duty gasoline vehicle - Run Liu; Hong-di He; Zhe Zhang; Cui-lin Wu; Jin-ming Yang; Xing-hang Zhu; Zhong-ren Peng (Journal of Cleaner Production, 2023)

Well-oriented immobilized immunoaffinity magnetic beads for detection of fumonisins in grains and feeds via pre-column automatic derivatization of high-performance liquid chromatography - Jinnan Chen; Meng Wang; Sen Li; Jin Ye; Li Li; Yu Wu; Di Cai; Tongtong Liu; Lin Zhu; Yi Shao; Songxue Wang (Food Chemistry, 2023)

Dendrobium officinale aqueous extract regulates bile acid synthesis to improve acute alcoholic liver injury in mice - Ju Ye; Di Wu; Xingdong Wu; Lin Qin; Mengting Yang; Yan-liu Lu; Dao-peng Tan; Yu-qi He (Food Bioscience, 2023)

Nitrogen addition promotes conservative resource-use strategies via aggravating phosphorus limitation of evergreen trees in subtropical forest - Changti Zhao; Quanhong Lin; Di Tian; Chengjun Ji; Haihua Shen; Dayong Fan; Xiangping Wang; Jingyun Fang (Science of The Total Environment, 2023)

Potential inhibitors of microglial activation from the roots of Wikstroemia lichiangensis W. W. Sm - Zisong Bai; Yingjie Wang; Qingqi Meng; Libin Xu; Gang Chen; Di Zhou; Bin Lin; Yue Hou; Ning Li (Phytochemistry, 2023)

Concentrations and controls of dissolved inorganic carbon in Arctic summer sea ice and adjacent surface seawaters - Xiaoxia Cai; Yanpei Zhuang; Yingxu Wu; Hongmei Lin; Di Qi (Marine Environmental Research, 2023)

A review of advances in mechanical behaviors of the underground energy transmission pipeline network under loads - Qiang Zheng; Qian Xu; Zekai Shu; Di Yang; Weiwang Chen; Nevzat Akkurt; Hui Zhang; Lin Lin; Xinxin Zhang; Yulong Ding (Gas Science and Engineering, 2023)

Theoretical study on stability evolution of soft and hard interbedded bedding reservoir slopes - Qiong Wu; Bo Zhang; Hui-ming Tang; Di Wang; Zhi-qi Liu; Zhi-wei Lin (Journal of Mountain Science, 2023)

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

Transcriptomic analysis reveals immune infiltration status and potential biomarkers of canine colorectal cancer - Zixiang Lin; Qi Chen; Jiajing Zhou; Jiatong Zhang; Xiaohu Zhang; Di Zhang; Jiahao Lin; Degui Lin (Veterinary Immunology and Immunopathology, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Alpine meadow patches unevenly regulate runoff and sediment yield generation on the Qinghai-Tibetan Plateau - Yu Liu; Di Wang; Zeng Cui; Shixiong Li; Runjie Li; Jesús Rodrigo-Comino; Manuel López-Vicente; Gao-Lin Wu (Journal of Hydrology, 2023)

Influence of circulation types on temporal and spatial variations of ozone in Beijing - Xiaowan Zhu; Jin Wu; Guiqian Tang; Lin Qiao; Tingting Han; Xiaomei Yin; Xiangxue Liu; Ziming Li; Yajun Xiong; Di He; Zhiqiang Ma (Journal of Environmental Sciences, 2023)

Improvement of hydrolysis efficiency and interfacial properties of zein using nanoemulsions prepared by a low energy emulsification method - Jia-Ling He; Bo-Hao Liu; Han-Lin Zhang; Di Xu; Bao-Ming Shi; Ying-Hua Zhang (Food Bioscience, 2023)

Physiologically-Based Pharmacokinetic Modeling of PAXLOVID™ with First-Order Absorption Kinetics - Kazuko Sagawa; Jian Lin; Rohit Jaini; Li Di (Pharmaceutical Research, 2023)

Effects of poplar agroforestry systems on soil nutrient and enzyme activity in the coastal region of eastern China - Cheng Xu; Zhuangzhuang Qian; Bo Wang; Tao Yang; Zeyang Lin; Di Tian; Changjun Ding; Luozhong Tang (Journal of Soils and Sediments, 2023)

Understanding the effects of tree-crop intercropping systems on crop production in China by combining field experiments with a meta-analysis - Tao Yang; Xueying Ouyang; Bo Wang; Di Tian; Cheng Xu; Zeyang Lin; Xiaomin Ge; Luozhong Tang (Agricultural Systems, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Reproductive toxicity of polystyrene nanoplastics in Drosophila melanogaster under multi-generational exposure - Qinghui Tu; Jianhao Deng; Miaomiao Di; Xiaorong Lin; Zhongzheng Chen; Bin Li; Ling Tian; Yuanyuan Zhang (Chemosphere, 2023)

Aging process does not necessarily enhance the toxicity of polystyrene microplastics to Microcystis aeruginosa - Di Wu; Lin Deng; Ting Wang; Wenchao Du; Ying Yin; Hongyan Guo (Science of The Total Environment, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

SERS determination of hydroxy-α-sanshool in spicy hotpot seasoning: The strategy to restrain the interference of capsaicin and its mechanism - Di Zhang; Yushan Fan; Xiaoxia Sun; Xiaoou Wei; Zitao Lin; Xinai Zhang; Jiyong Shi; Maurizio Battino; Yunyun Gong; Bolin Shi; Xiaobo Zou (Food Chemistry, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Research on hydrate-bearing reservoir deformation and wellbore wall stability during natural gas hydrate exploitation - Jianwei Li; Yu Zhang; Shengjie Di; Liang Lin; You Zhou (Geomechanics for Energy and the Environment, 2023)

Enhanced piezo-catalytic H2O2 production over Bi0.5Na0.5TiO3 via piezoelectricity enhancement and surface engineering - Yu Zhang; Yezhan Lin; Ruofan Li; Zhengran Chen; Di Zeng; Shuai Chen; Wenjing Wang; Ling Zhang; Wenzhong Wang; Hengchang Nie; Genshui Wang (Chemical Engineering Journal, 2023)

Challenges and opportunities in animal models of psoriatic arthritis - Lin-Kun Bai; Ya-Zhen Su; Zong-Di Ning; Cheng-Qiang Zhang; Li-Yun Zhang; Gai-Lian Zhang (Inflammation Research, 2023)

Carbon quantum dot fluorescent probe for labeling and imaging of stellate cell on liver frozen section below freezing point - Yan-Fei He; Kai Cheng; Zi-Tao Zhong; Xiao-Lin Hou; Chang-Zhi An; Jing Zhang; Wei Chen; Bo Liu; Jing Yuan; Yuan-Di Zhao (Analytica Chimica Acta, 2023)

Linking peptide-oriented surface imprinting magnetic nanoparticle with carbon nanotube-based fluorescence signal output device for ultrasensitive detection of glycoprotein - Shi-Song Yu; Yu-Jun Shi; Di Wang; Ti-Ti Qiang; Ya-Qi Zhao; Xin-Yu Wang; Jia-Meng Zhao; Lin-Yi Dong; Ya-Jie Huang; Xian-Hua Wang (Analytica Chimica Acta, 2023)

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

Epipelagic mesozooplankton communities in the northeastern Indian Ocean off Myanmar during the winter monsoon - Ping Du; Dingyong Zeng; Feilong Lin; Sanda Naing; Zhibing Jiang; Jingjing Zhang; Di Tian; Qinghe Liu; Yuanli Zhu; Soe Moe Lwin; Wenqi Ye; Chenggang Liu; et al. (Acta Oceanologica Sinica, 2023)

Target and non-target analysis of organochlorine pesticides and their transformation products in an agrochemical-contaminated area - Di Huang; Lirong Gao; Shuai Zhu; Lin Qiao; Yang Liu; Qiaofeng Ai; Chi Xu; Wenwen Wang; Meiling Lu; Minghui Zheng (Chemosphere, 2023)

Photodegradation behavior and mechanism of dibutyl phthalate in water under flood discharge atomization - Li Lin; Sheng Zhang; Lei Dong; Yueqi Cao; Wei Zhang; Xiong Pan; Yi Li; Chi Zhang; Jingxiang Tao; Di Jia; John Crittenden (Science of The Total Environment, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

Distribution of environmentally persistent free radicals in size-segregated PMs emitted from residential biomass fuel combustion - Jinfeng Zhao; Lin Shi; Jianwu Shi; Hao Li; Di Lang; Zhuo Wei; Shunling Li; Bo Pan (Journal of Hazardous Materials, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Inactivation of Microcystis aeruginosa by H2O2 generated from a carbon black polytetrafluoroethylene gas diffusion electrode in electrolysis by low-amperage electric current - Yuting Zhang; Li Lin; Di Jia; Lei Dong; Xiong Pan; Min Liu; Huawei Huang; Yuan Hu; John C. Crittenden (Environmental Pollution, 2023)

pH and non-enzymatic glucose response at ultra-low concentration using submicrochannel heterogeneous membrane - Yuan-Ju Tang; Kai Cheng; Lin-Fang Tan; Xiao-Ting Xie; Bin Zhang; Wen-Ming Su; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Double-negative T cells: a promising avenue of adoptive cell therapy in transplant oncology - Zhihang Hu; Modan Yang; Hao Chen; Chiyu He; Zuyuan Lin; Xinyu Yang; Huigang Li; Wei Shen; Di Lu; Xiao Xu (Journal of Zhejiang University-SCIENCE B, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

Punctiform Breakup and Initial Oceanization in the Central Red Sea Rift - Ya-Di Sang; Bakhit M. T. Adam; Chun-Feng Li; Liang Huang; Yong-Lin Wen; Jia-Ling Zhang; Yu-Tao Liu (Journal of Marine Science and Engineering, 2023)
The Central Red Sea Rift is a natural laboratory to study the transition from rifting to spreading. Based on new reflection seismic profiles and gravity modeling, we examined the crustal structure, tectonic evolution, breakup mechanism, and future evolution of the Central Red Sea Rift. Along this rift axis, the breakup of continental lithosphere is discontinuous and the oceanic crust is limited to the axial deeps. The punctiform breakup and formation of deeps is assisted by mantle upwelling and topographic uplift, but the nucleation is directly controlled by the normal-fault system. The discontinuities spaced between axial deeps within the relatively continuous central troughs are presently axial domes or highs and will evolve into new deeps with tectonic subsidence. Isolated deeps will grow and connect with each other to become a continuous central trough, before transitioning into a unified spreading center.

Identification and degradation of structural extracellular polymeric substances in waste activated sludge via a polygalacturonate-degrading consortium - Zhi-Yi Hu; Yi-Peng Lin; Qing-Ting Wang; Yi-Xin Zhang; Jie Tang; Si-Di Hong; Kun Dai; Shuai Wang; Yong-Ze Lu; Mark C.M. van Loosdrecht; Jianrong Wu; Raymond Jianxiong Zeng; et al. (Water Research, 2023)

Spatio-temporal variation of the relationship between air pollutants and land surface temperature in the Yangtze River Delta Urban Agglomeration, China - Yue Jiang; Wenpeng Lin; Di Xu; Dan Xu (Sustainable Cities and Society, 2023)

Collaborative optimization method and energy-saving, carbon-abatement potential evaluation for nearly-zero energy community supply system with different scenarios - Di Wu; Guangyao Fan; Yuxuan Duan; Ao Liu; Peiwen Zhang; Jiacheng Guo; Chengkai Lin (Sustainable Cities and Society, 2023)

Full-scale experimental study on dynamic behaviors of a three-cable network with a pretensioned cross-tie - Lin Chen; Lei Qin; Fangdian Di; Limin Sun; Yiqing Zou; Zhiquan Huang (Engineering Structures, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

To what extent the traffic restriction policies can improve its air quality? An inspiration from COVID-19 - Si-qing Xu; Hong-di He; Ming-ke Yang; Cui-lin Wu; Xing-hang Zhu; Zhong-ren Peng; Yuya Sasaki; Kenji Doi; Shinji Shimojo (Stochastic Environmental Research and Risk Assessment, 2023)

Mendelian Randomization Analysis Reveals No Causal Relationship Between Plasma α-Synuclein and Parkinson’s Disease - Qi Zhang; Zenan Lin; Yan He; Junhong Jiang; Di Hu (Molecular Neurobiology, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Citrate-promoted dissolution of nanostructured manganese oxides: Implications for nano-enabled sustainable agriculture - Di Fu; Lin Duan; Xiaoyan Li; Chuanjia Jiang; Tong Zhang; Wei Chen (Journal of Environmental Sciences, 2023)

Low GSK3β activity is required for insect diapause through responding to ROS/AKT signaling and down-regulation of Smad1/EcR/HR3 cascade - Zhe Song; Lin Tang; Zihan Liu; Di Wu (Insect Biochemistry and Molecular Biology, 2023)

A hybrid deep learning model for regional O3 and NO2 concentrations prediction based on spatiotemporal dependencies in air quality monitoring network - Cui-lin Wu; Hong-di He; Rui-feng Song; Xing-hang Zhu; Zhong-ren Peng; Qing-yan Fu; Jun Pan (Environmental Pollution, 2023)

Structure and hepatoprotective activity of Usp10/NF-κB/Nrf2 pathway-related Morchella esculenta polysaccharide - Shanshan Teng; Yongfeng Zhang; Xinghui Jin; Yanfeng Zhu; Lanzhou Li; Xiaowei Huang; Di Wang; Zhe Lin (Carbohydrate Polymers, 2023)

Simulated impacts of the wetter arid area of Northwestern China on the energy budget and atmospheric circulation over Tibetan Plateau and central part of North China plain in summer - Di Ma; Xianhong Meng; Shihua Lv; Yaohui Li; Haipeng Yu; Lele Shu; Lin Zhao; Zhaoguo Li (Atmospheric Research, 2023)

Identification and Characterization of Bacillus subtilis B9: A Diazotrophic Plant Growth-Promoting Endophytic Bacterium Isolated from Sugarcane Root - Yi-ning Di; Ling Kui; Pratiksha Singh; Lu-feng Liu; Lin-yan Xie; Li-lian He; Fu-sheng Li (Journal of Plant Growth Regulation, 2023)
Plant endophytic microorganisms, which can enhance plant growth and resistance to biotic and abiotic stresses, are untapped resources with large potential applications for crop production. However, the endophytic community is influenced by multiple factors, such as host genetics, the environment, and other microbes. Thus, it is important to characterize well-adapted endophytes from native crops. We isolated 43 endophytic bacteria from sugarcane cultivar Yunzhe-99-91. All these 43 isolates were examined in vitro for nitrogenase activity and the ability to dissolve phosphorus and produce siderophore. One of these strains, B9, identified as Bacillus subtilis and showed maximum plant growth promotion, was selected for detailed studies. B9 promoted the production of organic acids such as propionic acid, acetic acid, malic acid and citric acid, and the production of phytohormones, including indole-3-acetic acid, cytokinin, 6-benzyladenine, and zeatin. Moreover, B9 significantly promoted the growth of sugarcane plantlets and increased the content of nitrogen, phosphorus, and potassium in the seedlings by 29.26%, 50.78%, and 15.49%, respectively. The photosynthetic rate, root development, and chlorophyll content were also improved with varying degrees compared to the non-inoculated control. The cotyledon and hypocotyl of sugarcane gems germinated faster when co-cultured with the B9 strain compared with control group. Colonization assay showed that B9 was mainly colonized in the roots, followed by the stems and leaves. In conclusion, the positive interaction between endophytic strain B9 and sugarcane may provide long-lasting benefits and a direction for developing and utilizing B9 as a biofertilizer for sugarcane cultivation to decrease fertilizer application.

Butyl benzyl phthalate as a key component of phthalate ester in relation to cognitive impairment in NHANES elderly individuals and experimental mice - Yongquan Yu; Yucheng Wang; Yu Dong; Shuge Shu; Di Zhang; Jiayi Xu; Ying Zhang; Wei Shi; Shou-Lin Wang (Environmental Science and Pollution Research, 2023)

Dosing with pyrite significantly increases anammox performance: Its role in the electron transfer enhancement and the functions of the Fe-N-S cycle - Fan Feng; Zhigong Liu; Xi Tang; Xing Wu; Caiyan Qu; Seow Wah How; Di Wu; Ruiyang Xiao; Chong-Jian Tang; Zhang Lin; Liyuan Chai; Guang-Hao Chen (Water Research, 2023)

Olivine origination in lunar Das crater through three-dimensional numerical simulation - Huacheng Li; Zongyu Yue; Yangting Lin; Kaichang Di; Nan Zhang; Jianzhong Liu (Icarus, 2023)

Liver Organoids, Novel and Promising Modalities for Exploring and Repairing Liver Injury - Chiyu He; Di Lu; Zuyuan Lin; Hao Chen; Huigang Li; Xinyu Yang; Modan Yang; Kai Wang; Xuyong Wei; Shusen Zheng; Xiao Xu (Stem Cell Reviews and Reports, 2023)

Application of the rapid leaf A–Ci response (RACiR) technique: examples from evergreen broadleaved species - Quanhong Lin; Di Tian; Changti Zhao; Bin Wang; Zhengbing Yan; Benjamin D. Stocker; Yu’e Li; Jingyun Fang (Photosynthesis Research, 2023)

RBM3 interacts with Raptor to regulate autophagy and protect cardiomyocytes from ischemia–reperfusion-induced injury - Nan Wang; Limeiting Wang; Changyan Li; Peng Rao; Xun Wang; Yazhou Xu; Lin Yang; Lin Sun; Di Lu (Journal of Physiology and Biochemistry, 2023)

Correction to: Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2023)

Assessment of the spatiotemporal water quality variations in the Middle Route of China’s South-to-North Water Diversion Project by multivariate analysis - Yi Xu; Junqiang Lin; Xiaohui Lei; Di Zhang; Qidong Peng; Jia Wang; Boran Zhu (Environmental Science and Pollution Research, 2023)

Urban park use and self-reported physical, mental, and social health during the COVID-19 pandemic: An on-site survey in Beijing, China - Di Lin; Yan Sun; Yue Yang; Yi Han; Chengyang Xu (Urban Forestry & Urban Greening, 2023)

Facile synthesis of boric acid-functionalized magnetic covalent organic frameworks and application to magnetic solid-phase extraction of trace endocrine disrupting compounds from meat samples - Jin Liu; Zhuoqun Su; Qinfeng Xu; Yiheng Shi; Di Wu; Lin Li; Yongning Wu; Guoliang Li (Food Chemistry, 2023)

Research status, challenges and future prospects of renewable synthetic fuel catalysts for CO2 photocatalytic reduction conversion - Yujun Chen; Bin Guan; Xingze Wu; Jiangfeng Guo; Zeren Ma; Jinhe Zhang; Xing Jiang; Shibo Bao; Yiyan Cao; Chengdong Yin; Di Ai; Yuxuan Chen; et al. (Environmental Science and Pollution Research, 2022)

SIRT1-Enriched Exosomes Derived from Bone Marrow Mesenchymal Stromal Cells Alleviate Peripheral Neuropathy via Conserving Mitochondrial Function - Lizhen Shan; Fenfen Zhan; Detao Lin; Fabo Feng; Xinji Chen; Xiaolin Li; Di Yang (Journal of Molecular Neuroscience, 2022)

Microplastic pollution and its impact on marine microbes in Zhanjiang, China - Qing-Lang Song; Fang-Hong Nie; Di-Hua Zhu; Yun-Li Wei; Min Zhang; Yao Hu; Meng-Meng Chen; Dan-Ju Kang; Zhi-Bao Chen; Hong-Ying Lin; Jin-Jun Chen (Journal of Coastal Conservation, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

Plasma Lipidomic Subclasses and Risk of Hypertension in Middle-Aged and Elderly Chinese - Zhenhua Niu; Qingqing Wu; Yaogan Luo; Di Wang; He Zheng; Yanpu Wu; Xiaowei Yang; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2022)

Environmental decentralization, environmental public service, and public health: evidence from 289 cities in China - Huimin Ma; Danyang Di; Lin Li; Wei Zhang; Jianmei Wang (Environmental Geochemistry and Health, 2022)

Effects of carbonate alkalinity on branchial gene expression in the large-scale loach (Paramisgurnus dabryanus) - Mei Huang; Meng-Xiao Wu; Lin-Jiang Zhang; Di Mi; Yun-Long Zhang (Frontiers in Marine Science, 2022)
Elucidating the mechanisms of alkaline tolerance in freshwater teleosts will help in the development of commercial saline-alkaline aquaculture. The large-scale loach ( Paramisgurnus dabryanus ) is a viable species for such aquaculture, but the mechanisms of its tolerance of alkaline water are unclear. Large-scale loach was exposed to 40, 50, and 60 mmol L -1 NaHCO 3 for 12, 48, and 96 h to evaluate the transcriptional changes of branchial Rhesus (Rh) glycoproteins, and aquaporins (Aqp)1 and Aqp3. Rhag transcript levels increased with longer exposure times. Rhag expression also rose considerably at higher carbonate alkalinities. Rhbg mRNA levels declined significantly under carbonate alkalinity exposure. A marked up-regulation of Rhcg was observed in the gills of the loach. Exposure to 60 mmol L -1 NaHCO 3 also induced a significant up-regulation of aqp1 . By contrast, aqp3 expression was significantly lower after 48 h exposure. The current findings reveal that the large-scale loach up-regulates Rhag and Rhcg to enhance ammonia efflux from the gills when exposed to high alkalinity. It is proposed that this species maintains appropriate osmolality when adapting to an alkaline environment by down-regulating aqp3 (to impede urea removal) and up-regulating aqp1 in the gills (to excrete excessive internal water).

Applications, Challenges, and Outlook for PBPK Modeling and Simulation: A Regulatory, Industrial and Academic Perspective - Wen Lin; Yuan Chen; Jashvant D. Unadkat; Xinyuan Zhang; Di Wu; Tycho Heimbach (Pharmaceutical Research, 2022)

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Effects of Microplastics on Microbial Community in Zhanjiang Mangrove Sediments - Meng-Meng Chen; Fang-Hong Nie; Aftab Qamar; Di-hua Zhu; Yao Hu; Min Zhang; Qing-Lang Song; Hong-Ying Lin; Zhi-Bao Chen; Su-Qing Liu; Jin-Jun Chen (Bulletin of Environmental Contamination and Toxicology, 2022)

Develop a public response model of soundscape for urban landscape garden parks - Guoqing Di; Junli Xiang; Yao Yao; Cong Chen; Qinhao Lin (Urban Ecosystems, 2022)

High-efficiency adsorption of Cd(II) and Co(II) by ethylenediaminetetraacetic dianhydride-modified orange peel as a novel synthesized adsorbent - Fanghui Wang; Peng Wu; Lin Shu; Di Huang; Huanhuan Liu (Environmental Science and Pollution Research, 2022)

Effects of Environmental and Spatial Variables on Bacteria in Zhanjiang Mangrove Sediments - Di-Hua Zhu; Qing-Lang Song; Fang-Hong Nie; Wan Wei; Meng-Meng Chen; Min Zhang; Hong-Ying Lin; Dan-Ju Kang; Zhi-Bao Chen; Anthony G. Hay; Jin-Jun Chen (Current Microbiology, 2022)

Selenium Alleviates Inflammation in Staphylococcus aureus-Induced Mastitis via MerTK-Dependent Activation of the PI3K/Akt/mTOR Pathway in Mice - Si-jie Chen; Chen-yuan Zhang; Di Yu; Chang-jie Lin; Hao-jun Xu; Chang-min Hu (Biological Trace Element Research, 2022)

Optimizing river damming and impounding strategies to mitigate seawater intrusion in the coastal aquifer of Dagu River Basin, China - Di Zhang; Yun Yang; Jian Song; Jianfeng Wu; Xiaomin Sun; Jin Lin; Xiaobin Zhu; Jichun Wu (Hydrogeology Journal, 2022)

Simultaneous detection of ten kinds of insecticide residues in honey and pollen using UPLC-MS/MS with graphene and carbon nanotubes as adsorption and purification materials - Xiuyu Pang; Chenyu Li; Chuanjiang Zang; Lei Guan; Peng Zhang; Chunxiang Di; Nan Zou; Beixing Li; Wei Mu; Jin Lin (Environmental Science and Pollution Research, 2022)

Exogenous ascorbic acid application alleviates cadmium toxicity in seedlings of two wheat (Triticum aestivum L.) varieties by reducing cadmium uptake and enhancing antioxidative capacity - Zhen Zhou; Chang Wei; Haitao Liu; Qiujuan Jiao; Gezi Li; Jingjing Zhang; Biao Zhang; Weihuan Jin; Di Lin; Guo Chen; Suqin Yang (Environmental Science and Pollution Research, 2022)

P75 neurotrophin receptor controls subventricular zone neural stem cell migration after stroke - Sachin S. Deshpande; Subash C. Malik; Pasquale Conforti; Jia-di Lin; Yu-Hsuan Chu; Suvra Nath; Franziska Greulich; Meike-Ast Dumbach; N. Henriette Uhlenhaut; Christian Schachtrup (Cell and Tissue Research, 2022)
Stroke is the leading cause of adult disability. Endogenous neural stem/progenitor cells (NSPCs) originating from the subventricular zone (SVZ) contribute to the brain repair process. However, molecular mechanisms underlying CNS disease-induced SVZ NSPC-redirected migration to the lesion area are poorly understood. Here, we show that genetic depletion of the p75 neurotrophin receptor ( p75 NTR−/− ) in mice reduced SVZ NSPC migration towards the lesion area after cortical injury and that p75 NTR−/− NSPCs failed to migrate upon BDNF stimulation in vitro. Cortical injury rapidly increased p75 NTR abundance in SVZ NSPCs via bone morphogenetic protein (BMP) receptor signaling. SVZ-derived p75 NTR−/− NSPCs revealed an altered cytoskeletal network- and small GTPase family-related gene and protein expression. In accordance, BMP-treated non-migrating p75 NTR−/− NSPCs revealed an altered morphology and α-tubulin expression compared to BMP-treated migrating wild-type NSPCs. We propose that BMP-induced p75 NTR abundance in NSPCs is a regulator of SVZ NSPC migration to the lesion area via regulation of the cytoskeleton following cortical injury.

Id proteins: emerging roles in CNS disease and targets for modifying neural stemcell behavior - Yu-Hsuan Chu; Jia-di Lin; Suvra Nath; Christian Schachtrup (Cell and Tissue Research, 2022)
Neural stem/progenitor cells (NSPCs) are found in the adult brain and spinal cord, and endogenous or transplanted NSPCs contribute to repair processes and regulate immune responses in the CNS. However, the molecular mechanisms of NSPC survival and integration as well as their fate determination and functionality are still poorly understood. Inhibitor of DNA binding (Id) proteins are increasingly recognized as key determinants of NSPC fate specification. Id proteins act by antagonizing the DNA-binding activity of basic helix-loop-helix (bHLH) transcription factors, and the balance of Id and bHLH proteins determines cell fate decisions in numerous cell types and developmental stages. Id proteins are central in responses to environmental changes, as they occur in CNS injury and disease, and cellular responses in adult NSPCs implicate Id proteins as prime candidates for manipulating stemcell behavior. Here, we outline recent advances in understanding Id protein pleiotropic functions in CNS diseases and propose an integrated view of Id proteins and their promise as potential targets in modifying stemcell behavior to ameliorate CNS disease.

Isotherm, kinetics, and adsorption mechanism studies of diethylenetriaminepentaacetic acid—modified banana/pomegranate peels as efficient adsorbents for removing Cd(II) and Ni(II) from aqueous solution - Fanghui Wang; Peng Wu; Lin Shu; Qingbin Guo; Di Huang; Huanhuan Liu (Environmental Science and Pollution Research, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Role of the microRNA-29 family in myocardial fibrosis - Changyan Li; Nan Wang; Peng Rao; Limeiting Wang; Di Lu; Lin Sun (Journal of Physiology and Biochemistry, 2021)

Pest control ability, technical guidance, and pesticide overuse: evidence from rice farmers in rural China - Yanzhong Huang; Xiaofeng Luo; Di Liu; Sanxia Du; Aqian Yan; Lin Tang (Environmental Science and Pollution Research, 2021)

Combining ability and genetic diversity under low-temperature conditions at germination stage of maize (Zea mays L.) - Jiayue Zhang; Yichen Li; Ziwen Zhang; Hong Di; Lin Zhang; Xuerui Wang; Zhenhua Wang; Yu Zhou (Euphytica, 2021)

Calcium signalling mediated the regulation of growth and polysaccharide accumulation by light quality in Dendrobium officinale protocorms - Ting Lei; Suping Gao; Xiao Lin; Kaihui Zhang; Yingqi Liu; Wenji Li; Di Hu; Xiaofang Yu; Mingyan Jiang; Qibing Chen; Ying Sun (Horticulture, Environment, and Biotechnology, 2021)

Research on Roof Cutting and Pressure Releasing Technology of Cumulative Blasting in Deep and High Stress Roadway - Xiaojie Yang; Di Yuan; Haojie Xue; Yubing Gao; Xichun Tian; Jingchen Qi; Lin Hou; Jindong Cao (Geotechnical and Geological Engineering, 2021)

Pressure Distribution and Deformation Control of Gob-Side Entry Retaining Formed by Roof Cutting Influenced by Abandoned Roadways - Xiaojie Yang; Lin Hou; Haojie Xue; Di Yuan; Jindong Cao; Zijie Han; Yubing Gao (Geotechnical and Geological Engineering, 2021)

Injection route affects intra-articular hyaluronic acid distribution and clinical outcome in viscosupplementation treatment for knee osteoarthritis: a combined cadaver study and randomized clinical trial - Jun Xiao; Yong Hu; Lin Huang; Zhi-Fa Huang; Wei-Zhou Jiang; Yu-Qiang Luo; Meng-Yan Jia; Di Chen; Zhan-Jun Shi (Drug Delivery and Translational Research, 2021)

Land use and land cover change within the Koshi River Basin of the central Himalayas since 1990 - Fang-di Xie; Xue Wu; Lin-shan Liu; Yi-li Zhang; Basanta Paudel (Journal of Mountain Science, 2021)

Study on Mechanical Properties of Volcanic Breccia in Mahu Area, Xinjiang - Xiaojie Yang; Jindong Cao; Liu Yang; Ruifeng Huang; Di Yuan; Lin Hou (Geotechnical and Geological Engineering, 2020)

Identification of progranulin as a novel diagnostic biomarker for early-onset sepsis in neonates - Kai-Di Yang; Yu He; Sa Xiao; Qing Ai; Jia-Lin Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Global sensitivity analysis on a numerical model of seawater intrusion and its implications for coastal aquifer management: a case study in Dagu River Basin, Jiaozhou Bay, China - Di Zhang; Yun Yang; Jianfeng Wu; Xilai Zheng; Guanqun Liu; Xiaomin Sun; Jin Lin; Jichun Wu (Hydrogeology Journal, 2020)

Xanthatin mediates G 2 /M cell cycle arrest, autophagy and apoptosis via ROS/XIAP signaling in human colon cancer cells - Ya-di Geng; Lei Zhang; Guo-Yu Wang; Xiao-Jun Feng; Zhao-Lin Chen; Ling Jiang; Ai-Zong Shen (Natural Product Research, 2020)

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Bioaccessibility and health risk assessment of trace metals in soils of greenhouse vegetable production near the industrial areas of the Yangtze River Delta, China - Lanqin Yang; Lin Di; Feili Sun; Wenfei Tian; Biao Huang; Gang Fan (Environmental Science and Pollution Research, 2020)

Preparation of Novel ALRCs/nZVI Composite and Its Removal of Cr(VI) from Aqueous - Xuan Zhang; Xiao-qiang Cao; Guang Li; Jijie Yin; Di Zhang; Mingzhen Li; Na Meng; Liang Dong; Xian-jun Lyu; Lin Li; Jun Qiu; Yan Zhang; et al. (International Journal of Environmental Research, 2020)

α-Arbutin Protects Against Parkinson’s Disease-Associated Mitochondrial Dysfunction In Vitro and In Vivo - Yaqi Ding; Deqin Kong; Tong Zhou; Nai-di Yang; Chenqi Xin; Jiajia Xu; Qi Wang; Hang Zhang; Qiong Wu; Xiaomei Lu; Kahleong Lim; Bo Ma; et al. (NeuroMolecular Medicine, 2020)

Interspecific interactions in dual-species biofilms of soil bacteria: effects of fertilization practices - Xiaojie Sun; Peng Cai; Søren J. Sørensen; Monika Mortimer; Chunhui Gao; Qiaoyun Huang; Yiming Wang; Xiangui Lin; Yichao Wu; Di Zhu; Ruirui Chen (Journal of Soils and Sediments, 2020)

The acclimation of leaf photosynthesis of wheat and rice to seasonal temperature changes in T‐FACE environments - Chuang Cai; Gang Li; Lijun Di; Yunjie Ding; Lin Fu; Xuanhe Guo; Paul C. Struik; Genxing Pan; Haozheng Li; Weiping Chen; Weihong Luo; Xinyou Yin (Global Change Biology, 2020)
Crops show considerable capacity to adjust their photosynthetic characteristics to seasonal changes in temperature. However, how photosynthesis acclimates to changes in seasonal temperature under future climate conditions has not been revealed. We measured leaf photosynthesis ( A n ) of wheat ( Triticum aestivum L.) and rice ( Oryza sativa L.) grown under four combinations of two levels of CO 2 (ambient and enriched up to 500 µmol/mol) and two levels of canopy temperature (ambient and increased by 1.5–2.0°C) in temperature by free‐air CO 2 enrichment (T‐FACE) systems. Parameters of a biochemical C 3 ‐photosynthesis model and of a stomatal conductance ( g s ) model were estimated for the four conditions and for several crop stages. Some biochemical parameters related to electron transport and most g s parameters showed acclimation to seasonal growth temperature in both crops. The acclimation response did not differ much between wheat and rice, nor among the four treatments of the T‐FACE systems, when the difference in the seasonal growth temperature was accounted for. The relationships between biochemical parameters and leaf nitrogen content were consistent across leaf ranks, developmental stages, and treatment conditions. The acclimation had a strong impact on g s model parameters: when parameter values of a particular stage were used, the model failed to correctly estimate g s values of other stages. Further analysis using the coupled g s –biochemical photosynthesis model showed that ignoring the acclimation effect did not result in critical errors in estimating leaf photosynthesis under future climate, as long as parameter values were measured or derived from data obtained before flowering.

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Role of the prefrontal lobe in young normotensives with a family history of hypertension and hypertensives - Xiaoni Wang; Fadong Zhao; Saisai Yan; Xinzhu Zhang; Lin Xie; Binbin Liu; Xiaohui Di; Yi Li; Jianbao Zhang (Pflügers Archiv - European Journal of Physiology, 2019)

Gastrodin ameliorates microvascular reperfusion injury–induced pyroptosis by regulating the NLRP3/caspase-1 pathway - Wenjing Sun; Hongquan Lu; Lechun Lyu; Ping Yang; Zhi Lin; Ling Li; Lin Sun; Di Lu (Journal of Physiology and Biochemistry, 2019)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

Latest Progress of the Chinese Meteorological Satellite Program and Core Data Processing Technologies - Peng Zhang; Qifeng Lu; Xiuqing Hu; Songyan Gu; Lei Yang; Min Min; Lin Chen; Na Xu; Ling Sun; Wenguang Bai; Gang Ma; Di Xian (Advances in Atmospheric Sciences, 2019)

A global database of paired leaf nitrogen and phosphorus concentrations of terrestrial plants - Di Tian; Jens Kattge; Yahan Chen; Wenxuan Han; Yongkai Luo; Jinsheng He; Huifeng Hu; Zhiyao Tang; Suhui Ma; Zhengbing Yan; Quanhong Lin; Bernhard Schmid; et al. (Ecology, 2019)
Nitrogen (N) and phosphorus (P) are essential components of the basic cell structure of plants. In particular, leaf N and P concentrations and their stoichiometric relationship largely determine the photosynthesis, growth, reproduction, and ecophysiological processes of plants. As important leaf functional traits, leaf N and P concentrations and their stoichiometric relationship play vital roles in indicating plant nutrient‐use strategies and their evolution in terrestrial ecosystems. They also influence physiological and ecological processes in leaves (e.g., growth rate and energy metabolism) and productivity (e.g., net primary production and net ecosystem production) at ecosystem level. However, the lack of a comprehensive data set containing paired leaf N and P concentration records has distinctly limited research on nutrient stoichiometry and leaf functional traits. Here, we provide a global database of paired records of leaf N and P concentrations. A total of 11,354 individual records were acquired spanning 1,291 sites worldwide, including 201 families, 1,265 genera, and 3,227 species. The records span a latitudinal range of 45.28 °S to 68.35 °N and a longitudinal range of 155.5 °W to 168.0 °E. The variables provided for each individual record are (1) geographical location (longitude, latitude, and altitude); (2) matched leaf N and P concentrations and N:P ratio; (3) taxonomic information (family, genera, and species); (4) life form (angiosperm/gymnosperm, monocotyledonous/dicotyledonous and woody plants/herbaceous plants; note that woody plants were further divided into coniferous, deciduous broad‐leaved, and evergreen broad‐leaved woody species and that herbaceous plants were further divided into annual and perennial species); (5) mean annual temperature ( MAT ) and mean annual precipitation ( MAP ); and (6) soil N and P concentrations and pH value in some records. To date, this database is the world's largest database of paired leaf N and P concentrations, which contains matched information of geographical location, environmental factors, and taxa. We believe that the database will play a fundamental and crucial part of ecological stoichiometric studies. There are no copyright restrictions. When using this database, we kindly request that you cite this article, respecting all the authors’ hard work during sample collection and data compilation.

Relationship between warfarin dosage and international normalized ratio: a dose–response analysis and evaluation based on multicenter data - Ling Xue; Yuzhen Zhang; Cheng Xie; Ling Zhou; Linsheng Liu; Haiyan Zhang; Lianhong Xu; Hongtao Song; Meiqin Lin; Hanfan Qiu; Junrong Zhu; Yubing Zhu; et al. (European Journal of Clinical Pharmacology, 2019)

Heavy metal distribution, translocation, and human health risk assessment in the soil-rice system around Dongting Lake area, China - Lin Tang; Sihan Deng; Di Tan; Jiumei Long; Ming Lei (Environmental Science and Pollution Research, 2019)

Occurrence, speciation, and risks of trace metals in soils of greenhouse vegetable production from the vicinity of industrial areas in the Yangtze River Delta, China - Lanqin Yang; Guoming Liu; Lin Di; Xiangyang Wu; Wenhua You; Biao Huang (Environmental Science and Pollution Research, 2019)

Plantlet regeneration from primary callus cultures of Lilium brownii F.E.Br. ex Miellez var. giganteum G. Y. Li & Z. H. Chen, a rare bulbous germplasm - Yun Wu; Yi-Di Ma; Yue Li; Lin Zhang; Yi-Ping Xia (In Vitro Cellular & Developmental Biology - Plant, 2019)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

CXCL5 regulation of proliferation and migration in human non-small cell lung cancer cells - Lin Wang; Lin Shi; Jie Gu; Cheng Zhan; Junjie Xi; Jianyong Ding; Di Ge (Journal of Physiology and Biochemistry, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Effect of UGT2B7 genotypes on plasma concentration of valproic acid: a meta-analysis - Ping Wang; Xiao-Qian Lin; Wen-Ke Cai; Gui-Li Xu; Meng-Di Zhou; Mei Yang; Gong-Hao He (European Journal of Clinical Pharmacology, 2018)

CyberConnector: a service-oriented system for automatically tailoring multisource Earth observation data to feed Earth science models - Ziheng Sun; Liping Di; Haosheng Hao; Xiaoqing Wu; Daniel Q. Tong; Chen Zhang; Cora Virgei; Hui Fang; Eugene Yu; Xicheng Tan; Peng Yue; Li Lin (Earth Science Informatics, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

OPEN GLUME1: a key enzyme reducing the precursor of JA, participates in carbohydrate transport of lodicules during anthesis in rice - Xiaohui Li; Yihua Wang; Erchao Duan; Qi Qi; Kunneng Zhou; Qiuyun Lin; Di Wang; Yunlong Wang; Wuhua Long; Zhigang Zhao; Zhijun Cheng; Cailin Lei; et al. (Plant Cell Reports, 2018)

Di-(2-ethylhexyl)-phthalate induces glucose metabolic disorder in adolescent rats - Jin Xu; Liting Zhou; Shuyue Wang; Jian Zhu; Te Liu; Yiyang Jia; Di Sun; Huaiji Chen; Qi Wang; Feng Xu; Yuezhu Zhang; Hongbo Liu; et al. (Environmental Science and Pollution Research, 2018)

Intramuscular Delivery of scAAV9-hIGF1 Prolongs Survival in the hSOD1G93A ALS Mouse Model via Upregulation of D-Amino Acid Oxidase - HuiQian Lin; HaoJie Hu; WeiSong Duan; YaLing Liu; GuoJun Tan; ZhongYao Li; YaKun Liu; BinBin Deng; XueQin Song; Wan Wang; Di Wen; Ying Wang; et al. (Molecular Neurobiology, 2018)

A new cycloartane triterpenoid glycoside from Souliea vaginata - Hai-Feng Wu; Xin Liu; Yin-Di Zhu; Jing Zhou; Ying-Ying Gong; Guo-Xu Ma; Xu-Dong Xu; Yi-Lin Liu; Zheng-Hong Luo; Di-Zhao Chen; Qiong-Yu Zou; Zi-Jian Zhao (Natural Product Research, 2017)

Effect of herbicide used with years (8 + 1) on soil enzymic activity and microbial population diversity - Yumei Jiang; Di Lin; Xianjiao Guan; Jinfeng Wang; Guangpan Cao; Du Zhu; Chunrui Peng (Journal of Soils and Sediments, 2017)

Overexpression of Arabidopsis ICR1 gene affects vegetative growth and anthesis - Da-Hui Li; Man-Li Li; Xiao-Bo Yu; Di Wu; Huan Xi; Yi Lin; Yong-Ping Cai (Biologia, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Paleoseismic study of the Kamishiro Fault on the northern segment of the Itoigawa–Shizuoka Tectonic Line, Japan - Aiming Lin; Mikako Sano; Maomao Wang; Bing Yan; Di Bian; Ryoji Fueta; Takashi Hosoya (Journal of Seismology, 2017)

Antepartum hemorrhage from previous-cesarean-sectioned uterus as a potential sign of uterine artery pseudoaneurysm - Ning Zhang; Wei-hua Lou; Xue-bin Zhang; Jian-hua Lin; Wen Di (Journal of Zhejiang University-SCIENCE B, 2017)

Low humic acids promote in vitro lily bulblet enlargement by enhancing roots growth and carbohydrate metabolism - Yun Wu; Yi-ping Xia; Jia-ping Zhang; Fang Du; Lin Zhang; Yi-di Ma; Hong Zhou (Journal of Zhejiang University-SCIENCE B, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

The P450 oxidoreductase (POR) rs2868177 and cytochrome P450 (CYP) 2B6*6 polymorphisms contribute to the interindividual variability in human CYP2B6 activity - Li-chen Gao; Fang-qun Liu; Li Yang; Lin Cheng; Hai-ying Dai; Ran Tao; Shi-Peng Cao; Di Wang; Jie Tang (European Journal of Clinical Pharmacology, 2016)

Prevalence and phylogenetic characterization of canine coronavirus from diseased pet dogs in Beijing, China - Shuai Lu; Di Zhang; Jianfang Zhou; Zhaofei Xia; Degui Lin; Yongliang Lou; Wenjie Tan; Kun Qin (Science China Life Sciences, 2016)

Estimating crop chlorophyll content with hyperspectral vegetation indices and the hybrid inversion method - Liang Liang; Zhihao Qin; Shuhe Zhao; Liping Di; Chao Zhang; Meixia Deng; Hui Lin; Lianpeng Zhang; Lijuan Wang; Zhixiao Liu (International Journal of Remote Sensing, 2016)

Comparison of ultrastructural and physiological changes of potato (Solanum tuberosum L.) plantlets subjected to salt and modeling drought stresses - Jiang-Ping Bai; Hui-Juan Gao; Hong-Yu Yang; Yan Lou; Jun-Lian Zhang; Di Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Using hybrid transcription factors to study gene function in rice - Tao Zhao; Jun Liu; Hong-Yu Li; Jian-Zhong Lin; Ming-Di Bian; Chun-Yu Zhang; Yong-Xing Zhang; Yu-Chong Peng; Bin Liu; ChenTao Lin (Science China Life Sciences, 2015)

Mobilization of Diverse Transposable Elements in Rice Induced by Alien Pollination Without Entailing Genetic Introgression - Ying Wu; Tingting Jiang; Yue Sun; Zeyang Wang; Guizhen Guo; Shuai Sun; Jie Wang; Ning Li; Zhenhui Wang; Di Zhang; Yan Bai; Yang Gao; et al. (Plant Molecular Biology Reporter, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

Development of SNP-based dCAPS markers linked to major head smut resistance quantitative trait locus qHS2.09 in maize - Hong Di; Xianjun Liu; Qiankun Wang; Jianfeng Weng; Lin Zhang; Xinhai Li; Zhenhua Wang (Euphytica, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Effect of triclosan on reproduction, DNA damage and heat shock protein gene expression of the earthworm Eisenia fetida - Dasong Lin; Ye Li; Qixing Zhou; Yingming Xu; Di Wang (Ecotoxicology, 2014)

Genetic characterization of porcine kobuvirus and detection of coinfecting pathogens in diarrheic pigs in Jiangsu Province, China - Zhen Yang; Wenjie Jin; Zhenpeng Zhao; Weidong Lin; Di Zhang; Enqi Yu; Aijian Qin; Hanchun Yang (Archives of Virology, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

Baseline sensitivity and control efficacy of flutolanil in Rhizoctonia solani - Shandong Li; Yiping Hou; Di Peng; Lin Meng; Jianxin Wang; Mingguo Zhou; Changjun Chen (Australasian Plant Pathology, 2014)

Gridded Field Observations of Polybrominated Diphenyl Ethers in Soils of North China - Di Liu; Jin Ma; Xinghua Qiu; Yifan Zhao; Yan Lin; Qiaoyun Yang; Zhenji Gao; Tong Zhu (Archives of Environmental Contamination and Toxicology, 2014)

Ginseng Panaxoside Rb1 Reduces Body Weight in Diet-Induced Obese Mice - Ning Lin; Dong-Lian Cai; Di Jin; Yi Chen; Jiao-Jiao Shi (Cell Biochemistry and Biophysics, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Comprehensive screening for multi-class veterinary drug residues and other contaminants in muscle using column-switching UPLC-MS/MS - Jia Zhan; Di-ming Xu; Shi-jie Wang; Ji Sun; Yin-jun Xu; Mei-lin Ni; Ju-yi Yin; Jie Chen; Xue-jun Yu; Zhi-qiang Huang (Food Additives & Contaminants: Part A, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

The histone deacetylase inhibitor vorinostat prevents TNFα-induced necroptosis by regulating multiple signaling pathways - Di Wang; Ming Zhao; Guozhu Chen; Xiang Cheng; Xiaoxi Han; Song Lin; Xuhui Zhang; Xiaodan Yu (Apoptosis, 2013)

Quantitative analysis of the association between interleukin-10 1082A/G polymorphism and susceptibility to sepsis - Lin Ouyang; You-Di Lv; Can Hou; Guo-Bao Wu; Zhi-Hui He (Molecular Biology Reports, 2013)

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

The influence of chronic fluorosis on mitochondrial dynamics morphology and distribution in cortical neurons of the rat brain - Di-Dong Lou; Zhi-Zhong Guan; Yan-Jie Liu; Yan-Fei Liu; Kai-Lin Zhang; Ji-Gang Pan; Jin-Jing Pei (Archives of Toxicology, 2013)

Pharmacokinetics, Tissue Distribution, and Plasma Protein Binding Study of Platinum Originating from Dicycloplatin, a Novel Antitumor Supramolecule, in Rats and Dogs by ICP-MS - Di Zhao; Yongjie Zhang; Chunxiang Xu; Can Dong; Hui Lin; Lingli Zhang; Cuiyun Li; Shuangxia Ren; Xin Wang; Shuoye Yang; Deen Han; Xijing Chen (Biological Trace Element Research, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

A Common variant near the melanocortin 4 receptor is associated with low-density lipoprotein cholesterol and total cholesterol in the Chinese Han population - Liming Tao; Zhou Zhang; Zhuo Chen; Daizhan Zhou; Weidong Li; Mengyuan Kan; Di Zhang; Lin He; Guoying Huang; Yun Liu (Molecular Biology Reports, 2012)

QTL underlying field grain drying rate after physiological maturity in maize (Zea Mays L.) - Zhenhua Wang; Xia Wang; Lin Zhang; Xianjun Liu; Hong Di; Tingfeng Li; Xiaochun Jin (Euphytica, 2012)

Vegetative Ecological Characteristics of Restored Reed (Phragmites australis) Wetlands in the Yellow River Delta, China - Xuehong Wang; Junbao Yu; Di Zhou; Hongfang Dong; Yunzhao Li; Qianxin Lin; Bo Guan; Yongli Wang (Environmental Management, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Aircraft noise exposure affects rat behavior, plasma norepinephrine levels, and cell morphology of the temporal lobe - Guo-qing Di; Bing Zhou; Zheng-guang Li; Qi-li Lin (Journal of Zhejiang University-SCIENCE B, 2011)

VereFlu™: an integrated multiplex RT-PCR and microarray assay for rapid detection and identification of human influenza A and B viruses using lab-on-chip technology - Jeanette Teo; Patrizia Di Pietro; Floriana San Biagio; Monica Capozzoli; Yi-Mo Deng; Ian Barr; Natalie Caldwell; Kian-Leong Ong; Mitsuharu Sato; Rosemary Tan; Raymond Lin (Archives of Virology, 2011)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

Enhanced drought and salinity tolerance in transgenic potato plants with a BADH gene from spinach - Ning Zhang; Huai-Jun Si; Gang Wen; Hong-Hui Du; Bai-Lin Liu; Di Wang (Plant Biotechnology Reports, 2011)

Interspecific hybrids between Chrysanthemum grandiflorum (Ramat.) Kitamura and C. indicum (L.) Des Moul. and their drought tolerance evaluation - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Genetic polymorphisms of DNA repair gene XRCC1 and risk of uterine leiomyoma - Yang Yang; Xian Dun Zhai; Lin Bo Gao; Shi Liu Li; Zheng Wang; Guo Di Chen (Molecular and Cellular Biochemistry, 2010)

Overexpression of the steroidogenic acute regulatory protein increases the expression of ATP-binding cassette transporters in microvascular endothelial cells (bEnd.3) - Yan-xia Ning; Shun-lin Ren; Feng-di Zhao; Lian-hua Yin (Journal of Zhejiang University-SCIENCE B, 2010)

Establishment and maintenance of three Chinese human embryonic stem cell lines - Di Zhou; Ge Lin; Chang-Qing Xie; Bo Xiong; Xiao-Ying Zhou; Xiao-Bing Qian; Yi Liao; Guang-Xiu Lu (In Vitro Cellular & Developmental Biology - Animal, 2010)

Oxidative degradation of chlorophenol derivatives promoted by microwaves or power ultrasound: a mechanism investigation - Giancarlo Cravotto; Arianna Binello; Stefano Di Carlo; Laura Orio; Zhi-Lin Wu; Bernd Ondruschka (Environmental Science and Pollution Research, 2010)

Microbiological Endogenous Processes in Biological Wastewater Treatment Systems - Xiao-Di Hao; Qi-Lin Wang; Jing-Yi Zhu; Mark C. M. Van Loosdrecht (Critical Reviews in Environmental Science and Technology, 2010)

Factors affecting seed set in the crosses between Dendranthema grandiflorum (Ramat.) Kitamura and its wild species - Chun-Qing Sun; Fa-Di Chen; Nian-Jun Teng; Zhao-Lei Liu; Wei-Min Fang; Xi-Lin Hou (Euphytica, 2010)

Characterization of the Mechanism of the Staphylococcus aureus Cell Envelope by Bacitracin and Bacitracin-Metal Ions - Zu-De Qi; Yi Lin; Bo Zhou; Xiao-Di Ren; Dai-Wen Pang; Yi Liu (The Journal of Membrane Biology, 2008)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Genetic variability in Gymnodiniaceae ITS regions: implications for species identification and phylogenetic analysis - Peng Shao; Yue-Qin Chen; Hui Zhou; Jie Yuan; Liang-Hu Qu; Di Zhao; Yong-Shui Lin (Marine Biology, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)